A hydrophilic coating film and a hydrophilic coating liquid, and a method for forming a hydrophilic coating film
Patent Information
- Application Number
- CN202580013949.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-03-14
- Filing Date
- 2025-05-29
- Publication Date
- 2026-11-03
AI Technical Summary
Existing hydrophilic coatings are prone to reduced hydrophilicity and antifouling properties under environmental stress, making it difficult to remove dirt by washing with water, and it is difficult to form a durable coating at room temperature.
An inorganic porous coating membrane with nanoscale pores and a hydrophilic organic compound immersed in the pores are combined with a betaine polymer to form a coating membrane via a sol-gel method, which is then washed with water at room temperature.
It achieves the formation of a coating film with excellent hydrophilicity and antifouling properties at room temperature, which can maintain the hydrophilic function for a long time, and dirt can be easily washed away with water. The coating film also has excellent strength and weather resistance.
Smart Images

Figure CN123036348A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a hydrophilic coating film and a hydrophilic coating liquid, and to a method for forming the hydrophilic coating film. Background Technology
[0002] As an example of coating inorganic particles with hydrophilic resin, a hydrophilic coating film is disclosed, comprising: a fluororesin film coated on the surface of a substrate; first hydrophilic spherical particles coated on the fluororesin film, some of which are embedded in the fluororesin film while others are exposed; and second hydrophilic particles coated on the fluororesin film, some of which are embedded in the fluororesin film while others are exposed; wherein the average particle size of the first hydrophilic spherical particles is 25 μm or more and 700 μm or less, and the average particle size of the second hydrophilic particles is 0.05 μm or more and 2 μm or less (see Patent Document 1).
[0003] In addition, a surface treatment liquid and its hydrophilic treatment method are disclosed. In a polymeric composition containing a polymeric compound (A), a polymerization initiator (B), inorganic microparticles (C), and a solvent (S), a polymeric betaine compound (A1) having an ethylene unsaturated double bond and a betaine structure, and an adhesive polymeric compound (A2) having an ethylene unsaturated double bond and a specific type of adhesive group are used as polymeric compound (A). A water-soluble free radical polymerization initiator (B1) is used as polymerization initiator (B). Inorganic microparticles (C) having functional groups capable of forming covalent bonds with the polymer of polymeric compound (A) are used. Existing technical documents Patent documents
[0004] Patent Document 1: Japanese Patent Application Publication No. 2019-89930 Patent Document 2: Japanese Patent Application Publication No. 2022-129100 Summary of the Invention The problem that the invention aims to solve
[0005] In the hydrophilic coating film disclosed in Patent Document 1, due to the stress generated by the environment in which it is used, the first hydrophilic spherical particles and the second hydrophilic particles covering the fluororesin film will gradually peel off from the fluororesin film, and its hydrophilicity will gradually decrease, thus it cannot maintain its hydrophilic function for a long time. When the hydrophilicity of the hydrophilic coating film decreases, dust and other dirt adhering to the hydrophobic fluororesin film with a large water contact angle become difficult to wash off with water. The dirt cannot be easily washed off the substrate surface by water, and the dirt remains on the substrate surface, thus the substrate surface cannot be cleaned.
[0006] In the polymerizable composition and hydrophilic treatment method disclosed in Patent Document 2, to improve adhesion to inorganic particles, a polymerizable compound, a polymerization initiator, and inorganic particles are mixed, a coating film is formed on the object to be treated, polymerization is carried out by heating, and the resin film is fixed by bonding the resin film to the surface of the object to be treated. Therefore, if only coating is performed without heating, it can be easily washed away during the water washing process. Furthermore, under conditions such as outdoor use, even just being exposed to rain can wash away the hydrophilic polymeric compound, making it impossible to obtain a durable hydrophilic coating film. In many cases, heating the object to be treated is not possible; therefore, a durable hydrophilic coating film can be obtained simply by coating at room temperature and drying with a solvent.
[0007] The present invention aims to provide a hydrophilic coating film and a hydrophilic coating liquid for forming the hydrophilic coating film. The hydrophilic coating film has a small water contact angle on its surface, which increases the contact area between water droplets and the film surface. It also exhibits excellent hydrophilicity and antifouling properties, and adhering dirt can be easily washed away with water. Another objective of the present invention is to provide a hydrophilic coating film and a hydrophilic coating liquid for forming the hydrophilic coating film. This hydrophilic coating film can prevent the reduction of hydrophilicity and antifouling properties due to environmental stress and can maintain its hydrophilic and antifouling functions for a long period. Another objective of the present invention is to provide a method for forming a hydrophilic coating film. This method can produce a hydrophilic coating film that can be easily formed at room temperature without heating. Technical means to solve the problem
[0008] The hydrophilic coating film of the present invention is characterized by being formed of an inorganic porous coating film having a large number of pores of nanoscale size and a hydrophilic organic compound immersed in the pores of the inorganic porous coating film, and having a water contact angle of 20° or less as measured based on Japanese Industrial Standard (JIS) R 3257.
[0009] As an example of a hydrophilic coating film, the water contact angle measured based on the JIS R3257 standard is less than 10°.
[0010] As another example of a hydrophilic coating membrane, an inorganic porous coating membrane contains at least one inorganic microparticle selected from silicon dioxide (SiO2), aluminum oxide (Al2O3), zirconium dioxide (ZrO2), titanium dioxide (TiO2), and cerium dioxide (CeO2).
[0011] As another example of a hydrophilic coating membrane, an inorganic porous coating membrane has an inorganic nanoporous structure, which is prepared by a sol-gel method using at least one of silica sol, alumina sol, zirconium dioxide sol, titanium dioxide sol, and cerium dioxide sol.
[0012] As another example of a hydrophilic coating film, a hydrophilic organic compound contains a betaine polymer having both cationic and anionic sites within the same molecule.
[0013] As another example of a hydrophilic coating film, the proportion of betaine polymer in the hydrophilic organic compound is more than 20%.
[0014] As another example of a hydrophilic coating membrane, the porosity of the voids formed in the inorganic porous coating membrane is in the range of 20% to 70% relative to the volume of the inorganic porous coating membrane.
[0015] As another example of a hydrophilic coated film, the film thickness is in the range of 0.01~3μm.
[0016] As another example of a hydrophilic coating membrane, a hydrophilic organic compound impregnates into the pores of an inorganic porous coating membrane while simultaneously covering the surface of the inorganic porous coating membrane.
[0017] As another example of a hydrophilic coating film, the uppermost layer of the hydrophilic organic compound is located slightly below the surface of the inorganic porous coating film. The portion of the inorganic porous coating film exposed upward from the uppermost layer of the hydrophilic organic compound is coated with an extreme thin film formed by the hydrophilic organic compound, and fine irregularities are formed on the surface of the hydrophilic coating film.
[0018] The hydrophilic coating liquid involved in this invention is formed by an inorganic coating liquid and an organic coating liquid. The inorganic coating liquid is used to make an inorganic porous coating membrane with a large number of pores of nanoscale size. The organic coating liquid is used to make a hydrophilic organic compound containing a betaine polymer having cationic and anionic sites within the same molecule. The organic compound covers the inorganic porous coating membrane while being immersed in the pores of the inorganic porous coating membrane.
[0019] As an example of a hydrophilic coating liquid, the proportion of betaine polymer in the hydrophilic organic compound is more than 20%.
[0020] As another example of a hydrophilic coating solution, an inorganic coating solution contains at least one inorganic microparticle selected from silicon dioxide (SiO2), aluminum oxide (Al2O3), zirconium dioxide (ZrO2), titanium dioxide (TiO2), and cerium dioxide (CeO2), and the concentration of the solid component of the inorganic microparticle in the inorganic coating solution is 0.3 to 50 wt%.
[0021] As another example of a hydrophilic coating solution, the inorganic coating solution contains inorganic microparticles with an average particle size of less than 1 μm.
[0022] As another example of a hydrophilic coating solution, the content of hydrophilic organic compounds in an organic coating solution is in the range of 0.1 to 20 wt% relative to the total weight of the organic coating solution.
[0023] A method for forming a hydrophilic coating film comprising an inorganic porous coating film with numerous nano-sized pores and a hydrophilic organic compound includes: a washing step in which the surface of a specified substrate is washed with an alkaline detergent and then washed with an acidic liquid; an inorganic porous coating film forming step in which an inorganic coating liquid containing inorganic microparticles is applied to the surface of the substrate, and an inorganic porous coating film with numerous nano-sized pores is formed by a sol-gel method; a hydrophilic organic compound forming step in which an organic coating liquid containing a betaine polymer having cationic and anionic sites within the same molecule is applied to the surface of the substrate, and a hydrophilic organic compound containing the betaine polymer is formed on the surface of the substrate while the organic coating liquid is immersed in the pores of the inorganic porous coating film; and a water washing step in which the surface of the hydrophilic coating film formed by the inorganic porous coating film and the hydrophilic organic compound is washed with water.
[0024] As another example of a hydrophilic coating film formation method, in the inorganic porous coating film formation process, an inorganic porous coating film with an inorganic nanoporous structure is formed by using a sol-gel method that employs at least one of silica sol, alumina sol, zirconium dioxide sol, titanium dioxide sol, and cerium dioxide sol.
[0025] As another example of a method for forming a hydrophilic coating film, in the process of forming a hydrophilic organic compound, an organic coating liquid is used to cover the inorganic porous coating film in such a way that the inorganic porous coating film will not be exposed from the surface of the hydrophilic organic compound, so that the inorganic porous coating film is buried in the hydrophilic organic compound when forming the hydrophilic coating film.
[0026] In the hydrophilic organic compound formation process, an inorganic porous coating film is exposed from the top layer of the hydrophilic organic compound upwards. The inorganic coating liquid is applied to the surface of the substrate with the inorganic coating liquid positioned slightly below the surface of the inorganic porous coating film. Thus, during the formation of the hydrophilic coating film, the inorganic porous coating film is exposed from the top layer of the hydrophilic organic compound upwards. The portion of the inorganic porous coating film exposed from the top layer of the hydrophilic organic compound upwards is coated with an extremely thin film formed by the hydrophilic organic compound, and fine irregularities are formed on the surface of the hydrophilic coating film.
[0027] As another example of a method for forming a hydrophilic coating film, in a water washing process, excess hydrophilic organic compounds that are weakly bound to the pores of the inorganic porous coating film, other than those that are firmly bound to the pores of the inorganic porous coating film, are washed away by water, thereby removing hydrophilic organic compounds that do not contribute to the hydrophilicity from the hydrophilic coating film. Invention Effects
[0028] The hydrophilic coating membrane according to the present invention is formed from an inorganic porous coating membrane with a large number of pores of nanoscale size and a hydrophilic organic compound immersed in the pores of the inorganic porous coating membrane. The water contact angle measured based on the JIS R3257 standard is less than 20°. Therefore, it has excellent hydrophilicity and antifouling properties. The small contact angle between water and the membrane surface of the hydrophilic coating membrane can increase the contact area between water and the membrane surface. When the hydrophilic coating membrane is washed with water, the extensive contact between water and the membrane surface of the hydrophilic coating membrane can make the dirt attached to the hydrophilic coating membrane easy to wash away by water. In hydrophilic coatings, hydrophilic organic compounds penetrate into the numerous nanoscale pores of the inorganic porous coating. The hydrophilic organic compounds (hydrophilic organic membrane) are bound to the pores of the inorganic porous coating, thus giving the hydrophilic coating excellent strength. Furthermore, the hydrophilic organic compounds will not prematurely peel off or disappear from the hydrophilic coating due to stress generated by the usage environment. This prevents the hydrophilicity and antifouling properties of the hydrophilic coating from decreasing, and allows it to maintain the hydrophilic and antifouling functions provided by the hydrophilic organic compounds for a long time.
[0029] In hydrophilic coating membranes, since the water contact angle measured according to the JIS R3257 standard is less than 10°, the contact angle between water and the surface of the hydrophilic coating membrane is very small, resulting in excellent hydrophilicity and antifouling properties. This can reliably increase the contact area between water and the surface of the hydrophilic coating membrane. When washing the hydrophilic coating membrane with water, the large-scale contact between water and the surface of the hydrophilic coating membrane allows the dirt adhering to the hydrophilic coating membrane to be easily washed away by water.
[0030] In hydrophilic coatings, when the inorganic porous coating contains inorganic particles of silica (SiO2), hydrophilic organic compounds readily combine with the silica. These compounds, penetrating the numerous nanoscale micropores of the inorganic porous coating, readily bind within the silica-containing pores, resulting in a strong bond between the hydrophilic organic compounds and the porous structure. Similarly, when the inorganic porous coating contains inorganic particles of alumina (Al2O3), the hydrophilic organic compounds readily combine with the alumina. This allows the hydrophilic organic compounds penetrating the numerous nanoscale micropores of the inorganic porous coating to firmly bind within the alumina-containing pores. Furthermore, due to the effect of alumina, salts such as magnesium, calcium, sodium, and silicon become difficult to adhere to the hydrophilic coating, thus preventing contamination of the hydrophilic coating caused by the adhesion of these salts. In hydrophilic coatings, when the inorganic porous coating contains zirconium dioxide (ZrO2) microparticles, the hardness of the inorganic porous coating can be increased, thereby enhancing the rigidity of the hydrophilic coating. In the case of inorganic porous coatings containing titanium dioxide (TiO2) microparticles, the surface of the hydrophilic coating is covered with hydrophilic groups by the action of light and water on the titanium dioxide microparticles, thus imparting a self-cleaning effect. In the case of inorganic porous coatings containing cerium dioxide (CeO2) microparticles, the hardness of the inorganic porous coating can be increased, thereby enhancing the rigidity of the hydrophilic coating and imparting ultraviolet absorption. The hydrophilic coating solution binds the inorganic microparticles through covalent bonds, as well as through hydrogen bonds, ionic bonds, and van der Waals forces. In particular, by permeating the betaine polymer into nanoscale spaces, the binding capacity can be enhanced, and weather resistance can be maintained. Furthermore, when forming inorganic porous coating films, hydroxides of Ca, Na, Mg, K, B, salts, sodium silicate, resins, etc., can be added to improve adhesion to the substrate. Further, tetraalkoxysilanes, alkyltrialkoxysilanes, dialkyldialkoxysilanes, etc., can also be added.
[0031] In hydrophilic coatings, inorganic porous coatings possess an inorganic nanoporous structure prepared by a sol-gel method using at least one of silica sol, alumina sol, zirconium dioxide sol, titanium dioxide sol, or cerium dioxide sol. Hydrophilic organic compounds are infiltrated into the numerous nano-sized micropores of this inorganic nanoporous structure. The hydrophilic organic compounds (hydrophilic organic membrane) are bound within the pores of the inorganic porous coating, resulting in excellent strength. Furthermore, the hydrophilic organic compounds do not prematurely peel off or disappear from the hydrophilic coating due to stress generated by the usage environment. The hydrophilic organic compounds can remain in the hydrophilic coating for a long time, preventing a decrease in its hydrophilicity and antifouling properties, and maintaining the hydrophilic and antifouling functions provided by the hydrophilic organic compounds over a long period.
[0032] In hydrophilic coating membranes, the hydrophilic organic compounds contain betaine polymers with both cationic and anionic sites within the same molecule. These hydrophilic organic compounds exhibit excellent hydrophilicity and antifouling properties, reliably reducing the contact angle between water and the membrane surface, reliably increasing the contact area between water and the membrane surface, and allowing for easy removal of dirt adhering to the hydrophilic coating membrane during washing with water due to the extensive contact between water and the membrane surface.
[0033] In hydrophilic coatings, betaine polymers, which have both cationic and anionic sites within the same molecule, account for more than 20% of the hydrophilic organic compounds. Therefore, the excellent hydrophilicity of betaine polymers can be fully utilized. Hydrophilic organic compounds can exhibit excellent hydrophilicity and antifouling properties, reliably reducing the contact angle between water and the surface of the hydrophilic coating, reliably increasing the contact area between water and the surface of the hydrophilic coating, and when washing the hydrophilic coating with water, the large-scale contact between water and the surface of the hydrophilic coating makes it easy to wash away dirt adhering to the hydrophilic coating.
[0034] In hydrophilic coating films, since the porosity of the voids formed in the inorganic porous coating film is in the range of 20-70% relative to the volume of the inorganic porous coating film, a sufficient number of nano-sized micro-voids are formed in the inorganic porous coating film. Hydrophilic organic compounds penetrate into these voids, thereby making full use of the excellent hydrophilicity and antifouling properties of the hydrophilic organic compounds (hydrophilic organic film). This can endow the hydrophilic coating film with excellent hydrophilicity and antifouling properties, and can also fully protect the surface of the substrate through the hydrophilic coating film. In hydrophilic coatings, the hydrophilic organic compounds (hydrophilic organic membranes) combine with the numerous micropores of the inorganic porous coating membrane, resulting in excellent strength. Furthermore, the hydrophilic organic compounds do not prematurely peel off or disappear from the hydrophilic coating membrane due to stress generated by the usage environment. The hydrophilic organic compounds remain in the hydrophilic coating membrane for a long time, preventing a decrease in the hydrophilicity and antifouling properties of the hydrophilic coating membrane. This allows the hydrophilic and antifouling functions provided by the hydrophilic organic compounds to be maintained for a long time.
[0035] In hydrophilic coating films, since the film thickness is in the range of 0.01~3μm, the hydrophilic coating film maintains the specified strength and can fully protect the surface of the substrate. In addition, the hydrophilic coating film has excellent flexibility and can deform with the surface of the substrate, thereby maintaining the coverage of the substrate surface by the hydrophilic coating film.
[0036] In hydrophilic coatings, hydrophilic organic compounds penetrate the pores of the inorganic porous coating and cover its surface. Therefore, the hydrophilic coating exhibits excellent hydrophilicity. Furthermore, the hydrophilic organic compounds do not prematurely peel off or disappear from the hydrophilic coating due to environmental stress. The long-term presence of these compounds within the coating prevents a decrease in its hydrophilicity and antifouling properties, thus maintaining the hydrophilic and antifouling functions provided by the hydrophilic organic compounds over a long period.
[0037] In hydrophilic coating films, the uppermost layer of hydrophilic organic compounds is located slightly below the surface of the inorganic porous coating film. The portion of the inorganic porous coating film exposed upwards from the uppermost layer of hydrophilic organic compounds is coated with a thin film formed by the hydrophilic organic compounds. Furthermore, fine irregularities are formed on the surface of the hydrophilic coating film. Therefore, through the hydrophilic organic compounds and the irregularities, the hydrophilic coating film has excellent hydrophilicity. Moreover, the hydrophilic organic compounds will not prematurely peel off or disappear from the hydrophilic coating film due to stress caused by the usage environment. The hydrophilic organic compounds exist in the hydrophilic coating film for a long time, which can prevent the hydrophilicity and antifouling properties of the hydrophilic coating film from decreasing, and can maintain the hydrophilic and antifouling functions brought by the hydrophilic organic compounds for a long time.
[0038] The hydrophilic coating liquid involved in this invention is formed from an inorganic coating liquid and an organic coating liquid. The inorganic coating liquid produces an inorganic porous coating membrane with a large number of pores, and the organic coating liquid produces a hydrophilic organic compound containing a betaine polymer having cationic and anionic sites within the same molecule. This compound covers the inorganic porous coating membrane while being immersed in the pores of the inorganic porous coating membrane. Therefore, by containing a hydrophilic organic compound with excellent hydrophilicity and antifouling properties, a hydrophilic coating membrane with a small contact angle relative to the membrane surface and an increased contact area between water and the membrane surface can be produced. This allows for the production of a hydrophilic coating membrane that can easily wash away adhering dirt with water. In a hydrophilic coating solution, hydrophilic organic compounds are immersed into the numerous nano-sized micropores of an inorganic porous coating membrane. The hydrophilic organic compounds (hydrophilic organic membrane) are bound to the pores of the inorganic porous coating membrane, which can produce a hydrophilic coating membrane with excellent strength. Furthermore, the hydrophilic organic compounds will not prematurely peel off or disappear from the hydrophilic coating membrane due to stress caused by the usage environment. Thus, it is possible to produce a hydrophilic coating membrane that can prevent the reduction of hydrophilicity and antifouling properties, and to produce a hydrophilic coating membrane that can maintain the hydrophilic and antifouling functions brought by the hydrophilic organic compounds for a long time.
[0039] In hydrophilic coating solutions, betaine polymers, which have both cationic and anionic sites within the same molecule, account for more than 20% of the hydrophilic organic compounds. Therefore, the excellent hydrophilicity of betaine polymers can be fully utilized, resulting in excellent hydrophilicity and antifouling properties of the hydrophilic organic compounds. This reliably reduces the contact angle between water and the membrane surface and reliably increases the contact area between water and the membrane surface. Furthermore, when washing the hydrophilic coated membrane with water, the extensive contact between water and the membrane surface allows for the creation of hydrophilic coated membranes where dirt adhering to them can be easily washed away.
[0040] In a hydrophilic coating solution, when the inorganic coating solution contains inorganic microparticles of silica (SiO2) and the solid component concentration of the inorganic microparticles of silica in the inorganic coating solution is 0.3~50 wt%, hydrophilic organic compounds immersed in the numerous nano-sized micropores of the inorganic porous coating film can easily bind in the silica-containing pores, thereby forming a hydrophilic coating film that can firmly bind the hydrophilic organic compounds to the pores of the inorganic porous coating film. In a hydrophilic coating solution, when the inorganic coating solution contains inorganic microparticles of aluminum oxide (Al2O3) and the solid component concentration of the inorganic microparticles of aluminum oxide in the inorganic coating solution is 0.3~50 wt%, a hydrophilic coating film can be made that allows hydrophilic organic compounds immersed in a large number of nano-sized micropores of an inorganic porous coating film to be firmly bound to the pores containing aluminum oxide. Furthermore, due to the presence of aluminum oxide, salts such as magnesium, calcium, sodium, and silicon become difficult to adhere to the hydrophilic coating film. Therefore, a hydrophilic coating film that can prevent contamination of the hydrophilic coating film caused by the adhesion of salts such as magnesium, calcium, sodium, and silicon to the hydrophilic coating film can be formed. In a hydrophilic coating solution, when the inorganic coating solution contains inorganic zirconium dioxide (ZrO2) particles and the solid content concentration of the inorganic zirconium dioxide particles in the inorganic coating solution is 0.3~50 wt%, an inorganic porous coating film with improved hardness can be fabricated, thereby forming a hydrophilic coating film that enhances rigidity. In a hydrophilic coating solution, when the inorganic coating solution contains inorganic titanium dioxide (TiO2) particles and the solid content concentration of the inorganic titanium dioxide particles in the inorganic coating solution is 0.3~50 wt%, by acting on the inorganic titanium dioxide particles with light and water, the surface of the hydrophilic coating film is covered with hydrophilic groups, forming a hydrophilic coating film exhibiting self-cleaning properties. In a hydrophilic coating solution, when the inorganic coating solution contains inorganic particles of cerium dioxide (CeO2) and the concentration of the solid component of the inorganic particles of cerium dioxide in the inorganic coating solution is 0.3~50 wt%, the hardness of the inorganic porous coating film can be improved, thereby enhancing the rigidity of the hydrophilic coating film and forming a hydrophilic coating film with ultraviolet absorption effect.
[0041] In hydrophilic coating solutions, because the average particle size of the inorganic particles contained in the inorganic coating solution is less than 1 μm, an inorganic nanoporous structure is formed in the inorganic porous coating film. By allowing hydrophilic organic compounds to penetrate into the numerous tiny pores of the inorganic nanoporous structure, the hydrophilic organic compounds (hydrophilic organic membrane) bind to the pores of the inorganic porous coating film. This allows for the production of hydrophilic coating films with excellent strength, and the hydrophilic organic compounds will not prematurely peel off or disappear from the hydrophilic coating film due to stress generated by the usage environment. Therefore, it is possible to produce hydrophilic coating films that prevent the reduction of hydrophilicity and antifouling properties, and to produce hydrophilic coating films that can maintain the hydrophilic and antifouling functions provided by the hydrophilic organic compounds for a long time. The hydrophilic coating solution binds the inorganic particles through covalent bonds, or through hydrogen bonds, ionic bonds, van der Waals forces, etc. In particular, by permeating the betaine polymer into the nanoscale space, the binding can be enhanced, thereby preventing the hydrophilic organic compounds from prematurely peeling off or disappearing from the hydrophilic coating.
[0042] In hydrophilic coating solutions, since the content of hydrophilic organic compounds in organic coating solutions is in the range of 0.1~20 wt% relative to the total weight of organic coating solutions, the excellent hydrophilicity and antifouling properties of hydrophilic organic compounds containing betaine polymers can be fully utilized. Hydrophilic coating films with excellent hydrophilicity and antifouling properties can be produced. Hydrophilic coating films with small contact angles with the membrane surface can be produced, which can increase the contact area between water and the membrane surface. Furthermore, hydrophilic coating films that can easily wash away the attached dirt with water can also be produced.
[0043] According to the hydrophilic coating film formation method of the present invention, in the inorganic coating film formation step, an inorganic coating liquid for making an inorganic porous coating film is used to form an inorganic nanoporous coating film with a large number of micropores of nanoscale size through a sol-gel method. In the hydrophilic organic compound formation step, an organic coating liquid for making a hydrophilic organic compound containing a betaine polymer having cationic and anionic sites in the same molecule is used. When the organic coating liquid is immersed in the large number of micropores of the inorganic porous coating film, a hydrophilic organic compound is formed on the surface of the substrate. Therefore, it has excellent hydrophilicity and antifouling properties, and can produce a hydrophilic coating film with a small contact angle with the film surface, which can increase the contact area between water and the film surface. It can also produce a hydrophilic coating film that can be easily washed away by water. In the method for forming a hydrophilic coating film, during the hydrophilic organic compound formation step, the hydrophilic organic compound is immersed into the numerous nanoscale micropores of the inorganic porous coating film. The hydrophilic organic compound (hydrophilic organic film) binds to the pores of the inorganic coating film, resulting in a hydrophilic coating film with excellent strength. Furthermore, the hydrophilic organic compound will not prematurely peel off or disappear from the hydrophilic coating film due to stress generated by the usage environment. This method can produce a hydrophilic coating film that prevents a decrease in hydrophilicity and antifouling properties, and can maintain the hydrophilic and antifouling functions provided by the hydrophilic organic compound for a long period. The hydrophilic coating liquid binds to inorganic particles through covalent bonds, or through hydrogen bonds, ionic bonds, van der Waals forces, etc. In particular, by permeating the betaine polymer into the nanoscale spaces, the binding can be enhanced, thereby producing a hydrophilic coating film that prevents premature peeling or disappearance of the hydrophilic organic compound from the hydrophilic coating film.
[0044] In the method for forming a hydrophilic coating film, in the inorganic porous coating film forming process, an inorganic porous coating film with an inorganic nanoporous structure is formed by using at least one of silica sol, alumina sol, zirconium dioxide sol, titanium dioxide sol, and cerium dioxide sol via a sol-gel method. Therefore, an inorganic porous coating film with a large number of nano-sized micropores can be reliably formed on the surface of the substrate. This allows for the production of hydrophilic coating films with excellent hydrophilicity and antifouling properties, small contact angle with the film surface, and increased contact area between water and the film surface. It also allows for the production of hydrophilic coating films that can be easily washed away with water. In the method for forming a hydrophilic coating film, during the process of forming a hydrophilic organic compound, the hydrophilic organic compound is immersed into a large number of nano-sized micropores in the inorganic porous coating film. The hydrophilic organic compound (hydrophilic organic film) is bound to the pores of the inorganic porous coating film, which can produce a hydrophilic coating film with excellent strength. Since the hydrophilic organic compound will not peel off or disappear from the hydrophilic coating film prematurely due to stress caused by the use environment, a hydrophilic coating film that can prevent the reduction of hydrophilicity and antifouling properties can be produced. A hydrophilic coating film that can maintain the hydrophilic and antifouling functions brought by the hydrophilic organic compound for a long time can be produced.
[0045] In the method for forming a hydrophilic coating film, during the hydrophilic organic compound forming step, an organic coating liquid is used to cover the inorganic porous coating film in a manner that prevents the inorganic porous coating film from being exposed from the surface of the hydrophilic organic compound. During the formation of the hydrophilic coating film, the inorganic porous coating film is embedded within the hydrophilic organic compound. Therefore, by covering the inorganic porous coating film with the hydrophilic organic compound, a hydrophilic coating film with excellent hydrophilicity can be produced. Furthermore, the hydrophilic organic compound remains within the hydrophilic coating film for a long period and will not prematurely peel off or disappear due to stress caused by the usage environment. This allows for the production of a hydrophilic coating film that prevents a decrease in hydrophilicity and antifouling properties, and enables the long-term maintenance of the hydrophilic and antifouling functions provided by the hydrophilic organic compound.
[0046] In the method for forming a hydrophilic coating film, during the hydrophilic organic compound formation step, an inorganic porous coating film is exposed from the top layer of the hydrophilic organic compound upwards. The inorganic coating liquid is applied to the surface of the substrate with the inorganic coating liquid positioned slightly below the surface of the inorganic porous coating film. During the formation of the hydrophilic coating film, the inorganic porous coating film is exposed from the top layer of the hydrophilic organic compound upwards. The portion of the inorganic porous coating film exposed from the top layer of the hydrophilic organic compound upwards is coated with a thin film formed by the hydrophilic organic compound. Furthermore, the surface of the hydrophilic coating film has fine irregularities. Therefore, through the hydrophilic organic compounds and the formed irregularities, a hydrophilic coating film with excellent hydrophilicity can be made. Moreover, the hydrophilic organic compounds will not be prematurely peeled off or disappear from the hydrophilic coating film due to stress caused by the usage environment. The hydrophilic organic compounds exist in the hydrophilic coating film for a long time. It is possible to make a hydrophilic coating film that can prevent the reduction of hydrophilicity and antifouling properties of the hydrophilic coating film, and to make a hydrophilic coating film that can maintain the hydrophilic and antifouling functions brought by the hydrophilic organic compounds for a long time.
[0047] In the method for forming a hydrophilic coating film, during the water washing process, excess hydrophilic organic compounds that are weakly bound to the pores of the inorganic porous coating film, except for those that are firmly bound to the pores of the inorganic porous coating film, are removed by rinsing with water. This removes hydrophilic organic compounds that do not contribute to the hydrophilicity from the hydrophilic coating film. Therefore, it is possible to produce a hydrophilic coating film containing hydrophilic organic compounds that are firmly bound to the pores of the inorganic porous coating film and have excellent hydrophilicity and antifouling properties. It is also possible to produce a hydrophilic coating film with a small contact angle with the film surface, which can increase the contact area between water and the film surface. Furthermore, it is possible to produce a hydrophilic coating film that can be easily washed away with water to remove attached dirt. Attached Figure Description
[0048] Figure 1 This is a schematic diagram illustrating an example of an inorganic porous coating film formed on the surface of a substrate. Figure 2 It is shown by Figure 1 A schematic diagram of an example of a hydrophilic coating film formed by an inorganic porous coating film and a hydrophilic organic compound. Figure 3 It is shown by Figure 1 A schematic diagram of another example of a hydrophilic coating formed by an inorganic porous coating membrane and a hydrophilic organic compound. Figure 4 This is a schematic diagram illustrating another example of an inorganic porous coating film formed on the surface of a substrate. Figure 5 It is shown by Figure 4 A schematic diagram of another example of a hydrophilic coating formed by an inorganic porous coating membrane and a hydrophilic organic compound. Figure 6 It is shown by Figure 4 A schematic diagram of another example of a hydrophilic coating formed by an inorganic porous coating membrane and a hydrophilic organic compound. Figure 7 This is a flowchart of a method for forming a hydrophilic coated film. Figure 8 It shows the dripping on Figure 2 A diagram showing the contact angle of water droplets on a hydrophilic coated film. Figure 9 It shows the dripping on Figure 3 A diagram showing the contact angle of water droplets on a hydrophilic coated film. Figure 10 It shows the dripping on Figure 5 A diagram showing the contact angle of water droplets on a hydrophilic coated film. Figure 11 It shows the dripping on Figure 6 A diagram showing the contact angle of water droplets on a hydrophilic coated film. Figure 12 These are figures illustrating Examples 1 to 4 of the hydrophilic coating film. Figure 13 These are figures illustrating Examples 5 to 8 of the hydrophilic coating film. Figure 14 The figures show comparative examples 1 to 4 of the hydrophilic coating film. Figure 15 These are figures showing comparative examples 5 to 8 of the hydrophilic coating film. Detailed Implementation
[0049] Referring to the accompanying drawings, the hydrophilic coating film, hydrophilic coating liquid, and method for forming the hydrophilic coating film according to the present invention will be described in detail below. It should be noted that... Figure 1 This is a schematic diagram showing an example of an inorganic porous coating film 13a formed on the surface 12 of a substrate 11. Figure 2 It is shown by Figure 1 A schematic diagram of an example of a hydrophilic coating film 10A formed by an inorganic porous coating film 13a and a hydrophilic organic compound 14. Figure 3 It is shown by Figure 1 A schematic diagram of another example of a hydrophilic coating film 10B formed by an inorganic porous coating film 13a and a hydrophilic organic compound 14. Figure 4 This is a schematic diagram showing another example of an inorganic porous coating film 13b formed on the surface 12 of a substrate 11. Figure 5 It is shown by Figure 4A schematic diagram of another example of a hydrophilic coating film 10C formed by an inorganic porous coating film 13b and a hydrophilic organic compound 14. Figure 6 It is shown by Figure 4 A schematic diagram of another example of a hydrophilic coating film 10D formed by an inorganic porous coated film 13b and a hydrophilic organic compound 14. Although in Figures 1-6 The inorganic microparticles 16 and the voids 15 of the inorganic porous coating films 13a and 13b are illustrated in a schematic diagram that is visible to the naked eye, but in reality, the inorganic microparticles 16 and the voids 15 cannot be seen with the naked eye.
[0050] Hydrophilic coating films 10A-10D are formed on the surface 12 (surface and inner surface) of the substrate 11 to which they are covered. The hydrophilic coating films 10A-10D are formed from inorganic porous coating films 13a and 13b and hydrophilic organic compounds 14, and are obtained by: applying (coating) an inorganic coating liquid that forms inorganic porous coating films 13a and 13b to the surface 12 of the substrate 11, forming inorganic porous coating films 13a and 13b on the surface 12 of the substrate 11, and then applying (coating) an organic coating liquid that forms hydrophilic organic compounds 14 to the surface 12 of the substrate 11, thereby forming hydrophilic organic compounds 14 on the surface 12 of the substrate 11.
[0051] The substrate 11 that becomes the covering of the hydrophilic coating films 10A to 10D includes metal (metal molded articles), plastic (plastic molded articles and molded articles with plastic as the outermost layer), glass (glass molded articles), rubber (rubber molded articles), leather (leather molded articles), wood (wood molded articles), paper (paper molded articles), and textiles using fibers (textile molded articles), etc., but the substrate 11 is not particularly limited. In addition, there are no particular limitations on each molded article, including all molded articles of specified shapes made of metal, plastic, glass, rubber, leather, wood, paper, synthetic fibers, natural fibers, textiles, etc.
[0052] As metals, there are iron, aluminum, duralumin, stainless steel, copper, gold, silver, titanium, nickel, and alloys. As plastics, there are polymethyl methacrylate, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, ABS, polycarbonate, polystyrene, epoxy, unsaturated polyester, melamine, diallyl phthalate, polyimide, urethane, nylon, polyethylene, polypropylene, polyvinyl chloride, and fluoropolymers such as polytetrafluoroethylene resin, polychlorotrifluoroethylene resin, polyvinylidene fluoride resin, polyvinyl fluoride resin, perfluoroalkoxy fluoropolymers, tetrafluoroethylene-hexafluoropropylene copolymer resin, ethylene-tetrafluoroethylene copolymer resin, and ethylene-chlorotrifluoroethylene copolymer resin. As rubbers, there are polybutadiene rubber, polyisoprene (natural rubber), styrene-butadiene rubber, nitrile rubber, EPM, EPDM, epichlorohydrin rubber, chloroprene rubber, polysulfide rubber, and butyl rubber.
[0053] The inorganic coating solution uses any one of the following sols, or two or more of these sols: silica sol, which is formed by dispersing nano-sized inorganic particles 16 (colloidal particles) composed of multiple fine silica (SiO2) in a dispersion medium; alumina sol, which is formed by dispersing nano-sized inorganic particles 16 (colloidal particles) composed of multiple fine alumina (Al2O3) in a dispersion medium; zirconium dioxide sol, which is formed by dispersing nano-sized inorganic particles 16 (colloidal particles) composed of multiple zirconium dioxide (ZrO2) in a dispersion medium; titanium dioxide sol, which is formed by dispersing nano-sized inorganic particles 16 (colloidal particles) composed of multiple titanium dioxide (TiO2) in a dispersion medium; and cerium dioxide sol, which is formed by dispersing nano-sized inorganic particles 16 (colloidal particles) composed of multiple cerium dioxide (CeO2) in a dispersion medium. For the dispersion medium, water or alcohols such as ethanol, n-propanol, isopropanol, and n-butanol can be used, but this method is not limited to these.
[0054] Silica sol is prepared via the water glass method and the alkoxide method. It should be noted that the preparation of silica sol is not limited to these methods; other methods can also be used. The water glass method involves diluting sodium silicate (Na₂O·SiO₂) with water to a concentration of several percent to prepare an aqueous solution. This aqueous solution is then added in small, incremental increments to a preheated aqueous solution of sodium hydroxide to allow a reaction. After the reaction, the solution is boiled and refluxed for several hours, followed by ultrafiltration to obtain an alkaline silica sol. Next, impurities are removed through ion exchange, and a stabilizer is added to stabilize the solution, thus preparing the silica sol (silica gel solution).
[0055] The alkoxide method involves adding pure water to an alkyl silicate (tetraalkoxysilane) for hydrolysis, then removing the generated alcohol by distillation, and finally adjusting the pH to a specified value by adding a pH adjuster (such as a base like tetraalkylammonium hydroxide or an acid like hydrochloric acid). After adjusting the pH, the solution is concentrated by reflux to prepare silica sol (silica gel solution).
[0056] One example of a method for preparing alumina sol is to hydrothermally treat an alumina gel neutralized with a alkali in the presence of an organic acid to prepare an alumina sol (alumina colloidal solution). Another example is to hydrothermally treat an alumina gel obtained by a liquid-phase neutralization reaction of an acidic aluminum compound and an alkaline substance in the presence of a monovalent inorganic acid to prepare an alumina sol (alumina colloidal solution). Yet another example is to hydrothermally treat an alumina hydrate obtained by reacting a water-soluble aluminum salt with carbonic acid or carbonate, and then mix it with a monovalent acid to prepare an alumina sol (alumina colloidal solution).
[0057] Another example of a method for preparing alumina sol is: hydrothermally treating an alumina hydrate obtained by reacting a water-soluble aluminum salt with carbonic acid or carbonate, and then mixing it with a monovalent acid to prepare an alumina sol (alumina colloidal solution). Another example of a method for preparing alumina sol is: adding a new acid to an alumina hydrate obtained by hydrolyzing an aluminum alkoxide in a dilute acid aqueous solution, followed by hydrothermal degellation to prepare an alumina sol (alumina colloidal solution). Another example of a method for preparing alumina sol is: treating alumina powder in an aqueous phase with a strongly acidic cation exchange resin in the presence of an acid, then removing the ion exchange resin and cooling to room temperature to prepare an alumina sol (alumina colloidal solution). It should be noted that the preparation of alumina sol is not limited to these methods and can also be prepared by other methods.
[0058] One example of a method for preparing zirconium dioxide sol is as follows: An alkali is added to an aqueous solution containing a water-soluble zirconium salt such as zirconium oxychloride to generate zirconium hydroxide. The generated zirconium hydroxide is then hydrolyzed to prepare zirconium dioxide sol (zirconia colloidal solution). Another example of a method for preparing zirconium dioxide sol is as follows: The reaction product of ammonium zirconium carbonate and a chelating agent (e.g., hydroxyphenols, amino alcohols, hydroxy acids, polycarboxylic acids, hydroxy aldehydes, amino acids, and β-diketones) is hydrolyzed to prepare zirconium dioxide sol (zirconia colloidal solution). Yet another example of a method for preparing zirconium dioxide sol is as follows: An aqueous suspension containing zirconium hydroxide is kept at a temperature above 80°C to produce an aqueous suspension containing crystalline zirconium dioxide with a crystallinity of 80% or higher. A nitrogen-containing basic compound (primary amine, secondary amine, quaternary ammonium base), alkali metal, or alkaline earth metal hydroxide is added to the aqueous suspension containing crystalline zirconium dioxide to prepare an alkaline zirconium dioxide sol (zirconia colloidal solution).
[0059] Another example of a method for preparing zirconium dioxide sol is as follows: Zirconia sol (zirconia colloidal solution) is prepared by adding an alkali to an aqueous zirconium salt solution to precipitate it, adding an alkaline earth metal hydroxide or an aqueous solution thereof, and then heating the resulting suspension at a temperature of 90–200°C to mature it. Another example of a method for preparing zirconium dioxide sol is as follows: Zirconia sol (zirconia colloidal solution) is prepared by heating an aqueous zirconium salt solution having a molar ratio of anion to metal of 0.5:1 to 4:1 to 120–300°C, then cooling it to room temperature, and adjusting the pH to 2–6. Another example of a method for preparing zirconium dioxide sol is as follows: Zirconia sol (zirconia colloidal solution) is prepared by adding hydrogen peroxide in an amount approximately 1 / 2 molar ratio relative to the amount of zirconium in the solution to an aqueous zirconium salt solution with a concentration of 0.05–2.0 mol / L, heating it to 80–300°C, further adding an alkali such as ammonia, or treating it with an ion exchange resin, etc. It should be noted that the preparation of zirconium dioxide sol is not limited to these methods and can also be prepared by other methods.
[0060] One example of a method for preparing titanium dioxide sol is as follows: titanium hydroxide precipitated by adding an alkali to an aqueous solution of water-soluble titanium salts such as titanium tetrachloride or titanium sulfate is degelulated with strong acids such as hydrochloric acid or nitric acid to prepare titanium dioxide sol (titanium dioxide colloidal solution). Another example of a method for preparing titanium dioxide sol is as follows: titanium acid gel obtained by hydrolyzing water-soluble titanium salts with an alkali in the presence of a quaternary ammonium base is subjected to hydrothermal treatment to prepare titanium dioxide sol (titanium dioxide colloidal solution). Yet another example of a method for preparing titanium dioxide sol is as follows: adding organic amines such as alkali metal hydroxides, ammonium hydroxide, methylamine, trimethylamine, ethylenediamine, or ethanolamine to a gel obtained by reacting a water-soluble titanium compound with an alkali metal hydroxide or carbonate, or with an ammonium compound, and then subjecting the gel to hydrothermal treatment at a temperature above 100°C to prepare titanium dioxide sol (titanium dioxide colloidal solution). It should be noted that the preparation of titanium dioxide sol is not limited to these methods, and other methods can also be used.
[0061] One example of a method for preparing cerium dioxide sol is as follows: Cerium salt compounds such as cerium sulfate, cerium ammonium nitrate, cerium ammonium sulfate, cerium acetate, cerium chloride, cerium ammonium nitrate, cerium nitrate, and cerium nitrate are reacted with alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, and lithium hydroxide, or ammonia, at a temperature between 10°C and 90°C to form a gel. Then, acids such as hydrochloric acid, nitric acid, acetic acid, formic acid, lactic acid, and glycolic acid are added, and the mixture is subjected to hydrothermal treatment at a temperature above 100°C to prepare the cerium dioxide sol. The acid can also be added after the hydrothermal treatment.
[0062] Another example of a method for preparing cerium dioxide sol is as follows: cerium hydroxide or hydrated cerium hydroxide is dispersed in water, stirred, and then HNO3 is added to prepare a reaction dispersion. Cerium dioxide sol can also be prepared by heating the resulting reaction dispersion to approximately 80–150°C for about 6 hours. It should be noted that the preparation of cerium dioxide sol is not limited to these methods and can also be prepared by other methods.
[0063] The inorganic coating solution contains any one or more inorganic microparticles 16 selected from silicon dioxide (SiO2), aluminum oxide (Al2O3), zirconium dioxide (ZrO2), titanium dioxide (TiO2), and cerium dioxide (CeO2). By coating silicon dioxide sol, aluminum oxide sol, zirconium dioxide sol, titanium dioxide sol, and cerium dioxide sol onto the surface 12 of the substrate 11, a sol-gel method is used to form a coating solution. Figure 1 , Figure 4 The inorganic porous coating films 13a and 13b shown are inorganic nanoporous structures with a large number of fine micropores 15 (gap) of nanoscale size.
[0064] Figure 1In the inorganic porous coating 13a shown, a large number of generally spherical inorganic microparticles 16 are partially connected to each other, and a large number of nano-sized micropores 15 (inorganic nanoporous structure) are formed between these inorganic microparticles 16. Figure 4 In the inorganic porous coating 13b shown, irregularly shaped, generally columnar inorganic microparticles 16 are partially connected (linked) to each other, and a large number of nano-sized micropores 15 (inorganic nanoporous structure) are formed between these inorganic microparticles 16.
[0065] The solid concentration of inorganic microparticles 16 (silicon dioxide (SiO2), aluminum oxide (Al2O3), zirconium dioxide (ZrO2), titanium dioxide (TiO2), and cerium dioxide (CeO2)) in the inorganic coating solution is in the range of 0.3 wt% to 50 wt% relative to the total mass of the inorganic coating solution. If the solid concentration of inorganic microparticles 16 of silicon dioxide (SiO2) in the inorganic coating solution is less than 0.3 wt%, the amount of silicon dioxide that easily combines with the hydrophilic organic compound 14 becomes insufficient. The hydrophilic organic compound 14 that penetrates into the numerous micropores 15 of the inorganic porous coating films 13a and 13b (described later) becomes difficult to combine in the pores 15 containing silicon dioxide, thus preventing the hydrophilic organic compound 14 from being firmly bound to the pores 15 of the inorganic porous coating films 13a and 13b. Since the concentration of the inorganic silica (SiO2) inorganic microparticles 16 in the inorganic coating solution is within the aforementioned range, the hydrophilic organic compound 14 (hydrophilic organic membrane) immersed in the numerous micropores 15 of the inorganic porous coating membranes 13a and 13b easily binds in the silica-containing pores 15, thereby allowing the hydrophilic organic compound 14 to be firmly bound to the pores 15 of the inorganic porous coating membranes 13a and 13b.
[0066] If the solid concentration of inorganic alumina (Al2O3) particles 16 in the inorganic coating solution is less than 0.3 wt%, the amount of alumina that easily combines with the hydrophilic organic compound 14 becomes insufficient. The hydrophilic organic compound 14 that penetrates into the numerous micropores 15 of the inorganic porous coating membranes 13a and 13b becomes difficult to combine in the pores 15 containing alumina. As a result, the hydrophilic organic compound 14 cannot be firmly bound to the pores of the inorganic porous coating membranes 13a and 13b. Furthermore, the removal function of salts such as magnesium, calcium, sodium, and silicon brought about by alumina is reduced, and it is impossible to prevent the contamination of the hydrophilic coating membranes 10A to 10D caused by the adhesion of salts such as magnesium, calcium, sodium, and silicon. Since the concentration of the inorganic microparticles 16 of aluminum oxide (Al2O3) in the inorganic coating solution is within the aforementioned range, the hydrophilic organic compounds 14 that have penetrated into the numerous micropores 15 of the inorganic porous coating films 13a and 13b can be firmly bound to the pores 15 containing aluminum oxide. Furthermore, due to the effect of aluminum oxide, salts such as magnesium, calcium, sodium, and silicon become difficult to adhere to the hydrophilic coating films 10A to 10D. Therefore, contamination of the hydrophilic coating films 10A to 10D caused by the adhesion of salts such as magnesium, calcium, sodium, and silicon to the hydrophilic coating films 10A to 10D can be prevented.
[0067] If the solid concentration of the inorganic zirconium dioxide (ZrO2) particles 16 in the inorganic coating solution is less than 0.3 wt%, the hardness of the inorganic porous coating films 13a and 13b cannot be improved, thus the rigidity of the hydrophilic coating films 10A to 10D cannot be enhanced. Since the solid concentration of the inorganic zirconium dioxide (ZrO2) particles 16 in the inorganic coating solution is within the aforementioned range, the hardness of the inorganic porous coating films 13a and 13b can be improved, thereby enhancing the rigidity of the hydrophilic coating films 10A to 10D.
[0068] If the solid content concentration of the inorganic titanium dioxide (TiO2) particles 16 in the inorganic coating solution is less than 0.3 wt%, the amount of titanium dioxide becomes insufficient, and it cannot impart a self-cleaning effect to the hydrophilic coating films 10A-10D. Since the solid content concentration of the titanium dioxide (TiO2) particles 16 in the inorganic coating solution is within the aforementioned range, by applying light and water to the inorganic titanium dioxide particles 16, the surface of the hydrophilic coating films 10A-10D is covered with hydrophilic groups, thereby imparting an excellent self-cleaning effect to the hydrophilic coating films 10A-10D.
[0069] If the solid concentration of inorganic cerium dioxide (CeO2) particles 16 in the inorganic coating solution is less than 0.3 wt%, the hardness of the inorganic porous coating films 13a and 13b cannot be improved, and the rigidity of the hydrophilic coating films 10A to 10D cannot be enhanced. Furthermore, the ultraviolet absorption function cannot be fully obtained. Since the solid concentration of inorganic cerium dioxide (CeO2) particles 16 in the inorganic coating solution is within the aforementioned range, the hardness of the inorganic porous coating films 13a and 13b can be improved, thereby enhancing the rigidity of the hydrophilic coating films 10A to 10D. Additionally, the ultraviolet absorption effect of the hydrophilic coating films 10A to 10D can be obtained.
[0070] When the solid concentration of inorganic particles 16 (silicon dioxide (SiO2), aluminum oxide (Al2O3), zirconium dioxide (ZrO2), titanium dioxide (TiO2), and cerium dioxide (CeO2)) in the inorganic coating solution exceeds 50 wt%, a large number of inorganic particles 16 come into contact with each other over a wide area, and the inorganic particles 16 become dense, making it impossible to form a large number of micropores 15. Since the solid concentration of inorganic particles 16 in the inorganic coating solution is within the aforementioned range, inorganic porous coating films 13a and 13b with an inorganic nanoporous structure having a specified strength and a large number of micropores 15 of nanoscale size can be formed on the coating surface 12 of the substrate 11.
[0071] The inorganic particles 16 contained in the inorganic coating liquid have an average particle size of less than 1 μm. When the average particle size of the inorganic particles 16 exceeds 1 μm, the volume of the pores 15 increases, making it impossible to form inorganic porous coating films 13a and 13b with a large number of fine pores 15 on the coating surface 12 of the substrate 11. Since the average particle size of the inorganic particles 16 is less than 1 μm, a large number of fine inorganic particles 16 are partially connected to each other, thereby enabling the formation of inorganic porous coating films 13a and 13b with a large number of fine pores 15 of nanoscale size on the coating surface 12 of the substrate 11.
[0072] In the organic coating solution, a hydrophilic organic compound 14 containing a betaine polymer having both cationic and anionic sites within the same molecule is dispersed and mixed into the solvent. The content of the hydrophilic organic compound 14 in the organic coating solution is in the range of 0.1 wt% to 20 wt% relative to the total weight of the organic coating solution. If the content of the hydrophilic organic compound 14 in the organic coating solution is less than 0.1 wt%, the content of the hydrophilic organic compound 14 in the organic coating solution is relatively low, and the hydrophilic organic compound 14 obtained from the organic coating solution cannot exhibit sufficient hydrophilicity and antifouling properties, thus failing to impart excellent hydrophilicity and antifouling properties to the hydrophilic coating films 10A to 10D formed by the inorganic porous coating films 13a and 13b and the hydrophilic organic compound 14.
[0073] Since the content of hydrophilic organic compound 14 contained in the organic coating solution is within the aforementioned range, the organic coating solution contains a sufficient amount of hydrophilic organic compound 14. The hydrophilic organic compound 14 obtained from the organic coating solution exhibits sufficient hydrophilicity and antifouling properties, thereby imparting excellent hydrophilicity and antifouling properties to the hydrophilic coating films 10A~10D formed by inorganic porous coating films 13a, 13b and hydrophilic organic compound 14.
[0074] The proportion of betaine polymer in the hydrophilic organic compound 14 is more than 20%. If the proportion of betaine polymer in the hydrophilic organic compound 14 is less than 20%, the content of betaine polymer in the hydrophilic organic compound 14 is low, and the hydrophilic function of betaine polymer cannot be fully utilized. Therefore, the hydrophilic organic compound 14 prepared by the organic coating solution cannot exhibit sufficient hydrophilicity and antifouling properties, and thus cannot impart excellent hydrophilicity and antifouling properties to the hydrophilic coating films 10A~10D formed by the inorganic porous coating films 13a, 13b and the hydrophilic organic compound 14.
[0075] In the organic coating solution, since the proportion of betaine polymer in the hydrophilic organic compound 14 is more than 20%, the organic coating solution contains a sufficient amount of betaine polymer. The hydrophilic organic compound 14 prepared by the organic coating solution exhibits excellent hydrophilicity and antifouling properties, thereby endowing the hydrophilic coating films 10A~10D formed by inorganic porous coating films 13a, 13b and hydrophilic organic compound 14 with excellent hydrophilicity and antifouling properties.
[0076] As a specific example of an organic coating solution, a coating solution is used in which a polymer capable of forming a high-density polymer brush (surface-grafted polymer) as shown in the following structural formula (1) is dispersed in a water-soluble solvent or an ester-based solvent. The structural formula of the polymer capable of forming the high-density polymer brush is shown in (Chemical Formula 1).
[0077] (Chemical Formula 1)
[0078] The polymer capable of forming the high-density polymer brush shown in the structural formula (Chemical Formula 1) is a polymer brush of a carboxybetaine monomer having a silanol group at one end, and uses γ-mercaptopropyltrimethoxysilane as a chain transfer agent. This polymer capable of forming high-density polymer brushes can be used to produce blanket-like polymer films that resemble grown polymer chains.
[0079] In organic coating solutions, in addition to the polymers mentioned above that can form high-density polymer brushes (surface-grafted polymers), brush-like microparticles and bottle brush polymers can also be used. Furthermore, betaine polymers that do not contain silanol groups or alkoxysilyl groups at the ends or in the polymer chain can also be used. By using betaine polymers that do not contain silanol groups or alkoxysilyl groups, no reaction occurs in the solution, and long-term changes over time can be suppressed. As another example of a hydrophilic organic compound that can be used in combination with the betaine polymer in an organic coating solution, a coating solution containing the following polymers as another example can also be used, dispersed in an aqueous solvent or ester solvent: polymers capable of forming PHEMA polymer brushes, PHEMA polymers, polymers capable of forming PPEGMA polymer brushes, PPEGMA polymers, polymers capable of forming PNIPAM polymer brushes, PNIPAM polymers, polymers capable of forming PMTAC polymer brushes, PMTAC polymers, polymers capable of forming PSPMK polymer brushes, PSPMK polymers. Alternatively, a betaine polymer other than the betaine polymer shown in the structural formula (Chemical Formula 1) can be incorporated, or a coating solution containing, as another example, polymers capable of forming PMAPS polymer brushes, PMAPS polymers, polymers capable of forming PMPC polymer brushes, and PMPC polymers can be used. These polymers can also be obtained by copolymerizing a large number of monomers. The structural formula of the PHEMA polymer is shown in (Chemical Formula 2), but it may also have a silanol group or an alkoxysilyl group at one end, or it may contain a silanol group or an alkoxysilyl group in the polymer chain.
[0080] (Chemical Formula 2) The structural formula of PPEGMA polymer is shown in (Chemical Formula 3), but it may also have a silanol group or alkoxysilyl group at one end, or contain a silanol group or alkoxysilyl group in the polymer chain.
[0081] (Chemical Formula 3) The structural formula of the PNIPAM polymer is shown in (Chemical Formula 4), but it may also have a silanol group or alkoxysilyl group at one end, or contain a silanol group or alkoxysilyl group in the polymer chain.
[0082] (Chemical Formula 4) The structural formula of PMTAC polymer is shown in (Chemical Formula 5), but it may also have a silanol group or alkoxysilyl group at one end, or the polymer chain may contain a silanol group or alkoxysilyl group.
[0083] (Chemical Formula 5) The structural formula of the PSPMK polymer is shown in (Chemical Formula 6), but it may also have a silanol group or alkoxysilyl group at one end, or the polymer chain may contain a silanol group or alkoxysilyl group.
[0084] (Chemical Formula 6) The structural formula of PMAPS polymer is shown in (Chemical Formula 7), but it may also have a silanol group or alkoxysilyl group at one end, or contain a silanol group or alkoxysilyl group in the polymer chain.
[0085] (Chemical Formula 7) The structural formula of PMPC polymer is shown in (Chemical Formula 8), but it may also have a silanol group or alkoxysilyl group at one end, or contain a silanol group or alkoxysilyl group in the polymer chain.
[0086] (Chemical Formula 8) Water-soluble solvents can include primary alcohols, secondary alcohols, tertiary alcohols, ethers, esters, and ketones. For primary, secondary, or tertiary alcohols, isopropanol, sec-butanol, tert-butanol, and propylene glycol monomethyl ether are suitable. For ethers, tetrahydrofuran, 1,4-dioxane, 1,3-dioxolane, triethylene glycol butyl methyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol ethyl methyl ether, diethylene glycol isopropyl methyl ether, ethylene glycol diethyl ether, ethylene glycol dimethyl ether, propylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tripropylene glycol dimethyl ether, diethylene glycol butyl methyl ether, diethylene glycol dibutyl ether, and dipropylene glycol dimethyl ether are suitable.
[0087] For ester-based solvents, methyl acetate, ethyl acetate, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether propionate, γ-butyrolactone, etc., can be used. For ketone-based solvents, acetone, methyl ethyl ketone, methyl isobutyl ketone, diisopropyl ketone, cyclohexanone, etc., can be used. For aprotic solvents, dimethyl sulfoxide, N,N-dimethylformamide, and N-methylpyrrolidone, etc., can be used.
[0088] As another example of a betaine polymer constituting the polymer, the following betaine polymer can also be used. An example of a betaine polymer is a polymer containing 2-methacryloyloxyethyl phosphorylcholine. Its structural formula is shown in (Chemical Formula 9), but it may also have a silanol group or alkoxysilyl group at one end, or the polymer chain may contain a silanol group or alkoxysilyl group.
[0089] (Chemical Formula 9) Another example of a betaine polymer that constitutes a polymer is a polycarboxylated betaine polymer. The structural formula of a polycarboxylated betaine polymer is shown in (Chemical Formula 10), but it may also have a silanol group or an alkoxysilyl group at one end, or may contain a silanol group or an alkoxysilyl group in the polymer chain.
[0090] (Chemical Formula 10) The monomers constituting betaine polymers include: sulfobetaine monomer, carboxybetaine monomer, phosphorylbetaine monomer, dimethylamine oxide monomer, and dimethylsulfonyl propionate monomer. The general formula of sulfobetaine monomer is shown in (Chemical Formula 11), and its specific structural formulas are shown in (Chemical Formula 12) to (Chemical Formula 18).
[0091] (Chemical Formula 11)
[0092] (Chemical Formula 12) 3-((2-(methacryloyloxy)ethyl)dimethylammonium)propane-1-sulfonate
[0093] (Chemical Formula 13) 4-[(3-Methacrylamidopropyl)dimethylammonium]butane-1-sulfonate
[0094] (Chemical Formula 14) 3-((2-(acryloyloxy)ethyl)dimethylammonium)propane-1-sulfonate
[0095] (Chemical Formula 15) 3-[(3-Acrylamidopropyl)dimethylammonium]propane-1-sulfonate
[0096] (Chemical Formula 16) 4-[[2-(methacryloyloxy)ethyl]dimethylammonium]butane-1-sulfonate
[0097] (Chemical Formula 17) bis[2-(methacryloyloxy)ethyl](methyl)ammonium]propane-1-sulfonate
[0098] (Chemical Formula 18) 3-[(3-methacryloylaminopropyl)dimethylammonium]propane-1-sulfonate The general formula of the carboxybetaine monomer is shown in (Chemical Formula 19), and its specific structural formula is shown in (Chemical Formula 20) to (Chemical Formula 22).
[0099] (Chemical Formula 19)
[0100] (Chemical Formula 20) 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate
[0101] (Chemical Formula 21) 3-[[2-(methacryloyloxy)ethyl]dimethylammonium]propionate
[0102] (Chemical Formula 22) 3-[(3-acrylamidopropyl)dimethylammonium]propionate The general formula of the phosphate betaine monomer is shown in (Chemical Formula 23), and its specific structural formula is shown in (Chemical Formula 24).
[0103] (Chemical Formula 23)
[0104] (Chemical Formula 24) 2-(methacryloyloxy)ethyl 2-(trimethylammonium) ethyl phosphate The structural formula of dimethylamine oxide is shown in (Chemical Formula 25).
[0105] (Chemical Formula 25) The structural formula of methylsulfonate carboxylate is shown in (Chemical Formula 26).
[0106] (Chemical Formula 26) When the inorganic coating liquid forming the hydrophilic coating liquid contains at least one inorganic microparticle 16 selected from silicon dioxide (SiO2), aluminum oxide (Al2O3), zirconium dioxide (ZrO2), titanium dioxide (TiO2), and cerium dioxide (CeO2), and the solid component concentration of the inorganic microparticle 16 in the inorganic coating liquid is 0.3 to 50 wt%, inorganic porous coating films 13a and 13b with a large number of micropores 15 and sufficient strength can be formed by these inorganic microparticles 16, thereby making hydrophilic coating films 10A to 10D firmly bonded to the pores 15.
[0107] When the inorganic coating liquid forming the hydrophilic coating liquid contains inorganic microparticles 16 of silica (SiO2), by utilizing the easy binding property of the hydrophilic organic compound 14 with silica, the hydrophilic organic compound 14 immersed in the numerous micropores 15 of the inorganic porous coating films 13a and 13b can easily bind in the silica-containing pores 15, thereby producing hydrophilic coating films 10A to 10D in which the hydrophilic organic compound 14 is firmly bound in the pores 15 of the inorganic porous coating films 13a and 13b.
[0108] When the inorganic coating liquid forming the hydrophilic coating liquid contains inorganic microparticles 16 of aluminum oxide (Al2O3), by utilizing the easy binding of the hydrophilic organic compound 14 with aluminum oxide, it is possible to produce hydrophilic coating films 10A~10D in which the hydrophilic organic compound 14 immersed in the numerous micropores 15 of the inorganic porous coating films 13a, 13b is firmly bound to the pores 15 of the inorganic porous coating films 13a, 13b containing aluminum oxide. Furthermore, due to the effect of aluminum oxide, salts such as magnesium, calcium, sodium, and silicon become difficult to adhere to the hydrophilic coating films 10A~10D, thereby making it possible to produce hydrophilic coating films 10A~10D that can prevent contamination caused by the adhesion of salts such as magnesium, calcium, sodium, and silicon to the hydrophilic coating films 10A~10D.
[0109] When the inorganic coating solution forming the hydrophilic coating liquid contains inorganic particles 16 of zirconium dioxide (ZrO2), the zirconium dioxide can increase hardness, thereby enabling the fabrication of hydrophilic coating films 10A to 10D with improved rigidity. When the inorganic coating solution forming the hydrophilic coating liquid contains inorganic particles 16 of titanium dioxide (TiO2), the surface of the titanium dioxide inorganic particles 16 is covered with hydrophilic groups by the action of light and water, thereby enabling the fabrication of hydrophilic coating films 10A to 10D with excellent self-cleaning properties. When the inorganic coating solution forming the hydrophilic coating liquid contains inorganic particles 16 of cerium dioxide (CeO2), the cerium dioxide can increase hardness and also provide ultraviolet absorption capabilities, thereby enabling the fabrication of hydrophilic coating films 10A to 10D with improved rigidity and ultraviolet absorption capabilities.
[0110] Since the hydrophilic coating liquid is formed from an inorganic coating liquid and an organic coating liquid, the inorganic coating liquid is used to make inorganic porous coating membranes 13a and 13b with a large number of pores 15, and the organic coating liquid is used to make a hydrophilic organic compound 14. The hydrophilic organic compound 14 contains a betaine polymer (polymer brush) with cationic and anionic sites in the same molecule, and covers the inorganic porous coating membranes 13a and 13b in a state of being immersed in the pores 15. Therefore, by containing the hydrophilic organic compound 14 with excellent hydrophilicity and antifouling properties, hydrophilic coating membranes 10A to 10D with a small contact angle relative to the membrane surface and an increased contact area between water and the membrane surface can be made, and hydrophilic coating membranes 10A to 10D that can be easily washed away with water can be made.
[0111] By immersing the hydrophilic organic compound 14, which forms a hydrophilic coating liquid, into the numerous nano-sized micropores 15 of the inorganic porous coating membranes 13a and 13b, the hydrophilic organic compound 14 (hydrophilic organic membrane) is bonded (attached) to the pores 15 (inorganic microparticles 16) of the inorganic porous coating membranes 13a and 13b and the surface 12 of the substrate 11. This allows for the production of hydrophilic coating membranes 10A to 10D with excellent strength. Furthermore, the hydrophilic organic compound 14 will not prematurely peel off or disappear from the hydrophilic coating membranes 10A to 10D due to different stresses generated by the usage environment. Therefore, it is possible to produce hydrophilic coating membranes 10A to 10D that can prevent the reduction of hydrophilicity and antifouling properties, and to produce hydrophilic coating membranes 10A to 10D that can maintain the hydrophilic and antifouling functions brought by the hydrophilic organic compound 14 for a long time.
[0112] Figure 7 This is a flowchart of a method for forming a hydrophilic coated film of 10A to 10D. Based on Figure 7 An example of a method for forming hydrophilic coated films 10A to 10D will be described below. The method for forming hydrophilic coated films 10A to 10D is to form hydrophilic coated films 10A to 10D by means of inorganic porous coated films 13a and 13b having a large number of micropores 15 and hydrophilic organic compounds 14.
[0113] The method for forming a hydrophilic coating film includes: a washing step (P-1), an inorganic porous coating film formation step (P-2), a hydrophilic organic compound formation step (P-3), and a water washing step (P-4). By performing these steps (P-1) to (P-4), a hydrophilic coating film 10A to 10D is formed on the coating surface 12 of the substrate 11. The washing step (P-1) involves cleaning the coating surface 12 of the substrate 11 by blowing away dust using an air jet method such as an air gun, followed by washing the coating surface 12 of the substrate 11 with an alkaline detergent. After washing with the alkaline detergent, the coating surface 12 of the substrate 11 is washed with an acidic liquid. The alkaline detergent is not limited to any specific alkaline detergent, and the acidic liquid is not limited to any specific acidic liquid. In the washing process, by using an alkaline detergent to wash the coated surface 12 of the substrate 11 and by using an acidic liquid to wash the coated surface 12 of the substrate 11, it is possible to reliably remove contaminants such as dust, oil, and organic matter adhering to the coated surface 12 of the substrate 11.
[0114] The inorganic porous coating film formation process (P-2) involves coating (applying) an inorganic coating solution containing inorganic particles 16 onto the surface 12 of a washed substrate 11 using a sol-gel method employing at least one of silica sol, alumina sol, zirconium dioxide sol, titanium dioxide sol, and cerium dioxide sol. This forms inorganic porous coating films 13a and 13b on the coating surface 12 of the substrate 11, resulting in an inorganic nanoporous structure with numerous nano-sized micropores 15. Prior to the inorganic porous coating film formation process (P-2), an inorganic coating solution preparation process is performed: at least one of silica sol, alumina sol, zirconium dioxide sol, titanium dioxide sol, and cerium dioxide sol is dissolved in an aqueous solution (e.g., pure water) to prepare the inorganic coating solution.
[0115] The inorganic coating liquid can be applied to the coating surface 12 of the substrate 11 using any of the following methods: cloth coating (wiping coating method), in which the inorganic coating liquid penetrates into a cloth made of microfibers or nonwoven fabric and is then applied to the coating surface 12 of the substrate 11 through the cloth; spraying machine (spraying method), in which an inorganic coating liquid is applied to the coating surface 12 of the substrate 11 using a spray can or spray gun containing the inorganic coating liquid; brush coating, in which the inorganic coating liquid is applied to the coating surface 12 of the substrate 11 using brush bristles; roller coating machine, in which the inorganic coating liquid is applied to the coating surface 12 of the substrate 11 using a roller coated with the inorganic coating liquid; or spin coating machine (spin coating method), in which the inorganic coating liquid is placed on the coating surface 12 of the substrate 11 and then dispersed on the coating surface 12 of the substrate 11 by using the centrifugal force generated by rotating the substrate 11 at high speed.
[0116] In the inorganic porous coating film formation process (P-2), as described above, the aforementioned inorganic coating liquid containing at least one inorganic microparticle 16 selected from silicon dioxide (SiO2), aluminum oxide (Al2O3), zirconium dioxide (ZrO2), titanium dioxide (TiO2), and cerium dioxide (CeO2) is used. In the inorganic porous coating film formation process (P-2), after the inorganic coating liquid is coated onto the coating surface 12 of the substrate 11, the inorganic coating liquid is dried. In the inorganic porous coating film formation process (P-2), the dispersion medium (water or alcohol) contained in the inorganic coating liquid evaporates, and the inorganic microparticles 16 partially connect with each other. The inorganic porous coating films 13a and 13b formed in the inorganic porous coating film formation process (P-2) are as follows: Figure 1 , Figure 4 As shown, it has an inorganic nanoporous structure with a large number of fine micropores 15 of nanoscale size in the range of 20% to 70% porosity.
[0117] The hydrophilic organic compound formation process (P-3) is as follows: after inorganic porous coating films 13a and 13b with a large number of micropores 15 are formed on the coating surface 12 of the substrate 11, an organic coating liquid is coated (applied) from the top of the inorganic porous coating films 13a and 13b onto the coating surface 12 of the substrate 11, thereby forming a hydrophilic organic compound 14 on the coating surface 12 of the substrate 11.
[0118] The organic coating liquid can be applied to the inorganic porous coating membranes 13a and 13b (surface 12 of substrate 11) using any of the following coating methods: fabric coating, in which the organic coating liquid permeates into a fabric made of microfibers or nonwoven fabric and is applied to the surface 12 of substrate 11 through the fabric; spraying machine, using a spray can or spray gun containing the organic coating liquid to apply the organic coating liquid to the surface 12 of substrate 11; brush coating, using brush bristles to apply the organic coating liquid to the surface 12 of substrate 11; roller coating machine, using a roller coated with the organic coating liquid to apply the organic coating liquid to the surface 12 of substrate 11; spin coating machine, after placing the organic coating liquid on the surface 12 of substrate 11, using the centrifugal force generated by rotating substrate 11 at high speed to disperse the organic coating liquid on the surface 12 of substrate 11.
[0119] In the hydrophilic organic compound formation step (P-3), as described above, an organic coating liquid is used, wherein a hydrophilic organic compound 14 containing a betaine polymer having both cationic and anionic sites within the same molecule is dispersed and mixed in. In the hydrophilic organic compound formation step (P-3), the organic coating liquid is applied to the inorganic porous coating films 13a and 13b in a manner that prevents the inorganic porous coating films 13a and 13b from being exposed from the surface of the hydrophilic organic compound 14, according to a predetermined coverage size, thereby covering the surfaces of the inorganic porous coating films 13a and 13b with the organic coating liquid. Alternatively, the hydrophilic organic polymer coating liquid is applied to the inorganic porous coating films 13a and 13b in such a manner that the uppermost layer of the inorganic porous coating films 13a and 13b (inorganic microparticles 16) is exposed from the surface of the hydrophilic organic polymer coating liquid.
[0120] In the hydrophilic organic compound formation step (P-3), the hydrophilic organic compound 14 contained in the organic coating liquid is immersed in the numerous micropores 15 of the inorganic porous coating films 13a and 13b together with the organic coating liquid coated on the inorganic porous coating films 13a and 13b (surface 12 of substrate 11). In the hydrophilic organic compound formation step (P-3), the organic coating liquid immersed in the pores 15 is dried. The solvent in the organic coating liquid immersed in the pores 15 of the inorganic porous coating membranes 13a and 13b evaporates, the hydrophilic organic compound 14 hardens, and the hydrophilic organic compound 14 (hydrophilic organic membrane) combines (bonds) to the pores 15 (inorganic microparticles 16) of the inorganic porous coating membranes 13a and 13b and the surface 12 of the substrate 11, forming a hydrophilic coating membrane 10A~10D composed of the inorganic porous coating membranes 13a and 13b and the hydrophilic organic compound 14 (hydrophilic organic membrane).
[0121] In the hydrophilic organic compound formation process (P-3), when forming hydrophilic coating films 10A to 10D, inorganic porous coating films 13a and 13b do not protrude from the surface of hydrophilic organic compound 14. Hydrophilic organic compound 14 (hydrophilic organic film) covers the surface of inorganic porous coating films 13a and 13b (inorganic microparticles 16), and inorganic porous coating films 13a and 13b are buried in hydrophilic organic compound 14.
[0122] In addition, during the hydrophilic organic compound formation process (P-3), when forming the hydrophilic coating films 10A to 10D, the uppermost layer of the hydrophilic organic compound 14 (hydrophilic organic film) is located slightly below the surface of the inorganic porous coating films 13a and 13b. As a result, the uppermost layer of the inorganic porous coating films 13a and 13b (inorganic microparticles 16) is exposed upward from the uppermost layer of the hydrophilic organic compound 14. The portion of the inorganic porous coating films 13a and 13b (inorganic microparticles 16) that is exposed upward from the uppermost layer of the hydrophilic organic compound 14 (uppermost layer) forms fine irregularities on the surface of the hydrophilic organic compound 14, and the irregular portion (uppermost layer) is coated with an extremely thin film formed by the hydrophilic organic compound 14 (hydrophilic organic film).
[0123] The water washing process (P-4) involves passing water over the surface of the hydrophilic coating films 10A-10D, which are formed by inorganic porous coating films 13a and 13b and hydrophilic organic compounds 14 (hydrophilic organic films), and washing the hydrophilic coating films 10A-10D with water. In the water washing process (P-4), excess hydrophilic organic compounds 14 that are weakly bound to the inorganic porous coating films 13a and 13b, other than those that are firmly bound to the inorganic porous coating films 13a and 13b, are removed from the hydrophilic coating films 10A-10D by rinsing with water.
[0124] The method for forming a hydrophilic coating film is as follows: In the inorganic porous coating film forming step (P-2), an inorganic coating solution used to prepare inorganic porous coating films 13a and 13b is used to form inorganic porous coating films 13a and 13b with a large number of nano-sized micropores 15 through a sol-gel method. Furthermore, in the hydrophilic organic compound forming step (P-3), an organic compound 14 containing a betaine polymer having both cationic and anionic sites within the same molecule is used. The organic coating liquid is used to penetrate the numerous micropores 15 of the inorganic porous coating membranes 13a and 13b. Since the hydrophilic organic compound 14 forms a hydrophilic organic membrane on the surface 12 of the substrate 11, hydrophilic coating membranes 10A to 10D with excellent hydrophilicity and antifouling properties, small contact angle relative to the membrane surface, and increased contact area between water and the membrane surface can be produced. Hydrophilic coating membranes 10A to 10D that can easily wash away the attached dirt with water can also be produced.
[0125] The method for forming a hydrophilic coating film is as follows: In the hydrophilic organic compound forming process (P-3), the hydrophilic organic compound 14 is immersed into the numerous micropores 15 of the inorganic porous coating films 13a and 13b. The hydrophilic organic compound 14 (hydrophilic organic film) is bonded (joined) to the pores 15 (inorganic microparticles 16) of the inorganic porous coating films 13a and 13b and the surface 12 of the substrate 11. This method can produce hydrophilic coating films 10A to 10D with excellent strength. Furthermore, the hydrophilic organic compound 14 will not prematurely peel off or disappear from the hydrophilic coating films 10A to 10D due to stress generated by the usage environment. Therefore, it is possible to produce hydrophilic coating films 10A to 10D that can prevent the reduction of hydrophilicity and antifouling properties. It is also possible to produce hydrophilic coating films 10A to 10D that can maintain the hydrophilic and antifouling functions brought by the hydrophilic organic compound 14 for a long time.
[0126] The method for forming a hydrophilic coating film is as follows: In the washing process (P-1), the coating surface 12 of the substrate 11 is washed with an alkaline detergent (e.g., an alkaline detergent with a pH of 8 to 9) and the coating surface 12 of the substrate 11 is washed with an acidic liquid (e.g., an acidic liquid with a pH of 1 to 2). This method can reliably remove contaminants such as dust, oil, and organic matter adhering to the coating surface 12 of the substrate 11, and a hydrophilic coating film 10A to 10D with excellent hydrophilicity can be formed on the surface 12 of the substrate 11 after the dirt has been removed. In the inorganic porous coating film forming step (P-2) of the hydrophilic coating film forming method, inorganic porous coating films 13a and 13b with inorganic nanoporous structures are formed by using at least one of silica sol, alumina sol, zirconium dioxide sol, titanium dioxide sol, and cerium dioxide sol. In this way, inorganic coating films 13a and 13b with a large number of nano-sized micropores 15 can be reliably formed on the coating surface 12 of the substrate 11.
[0127] In the hydrophilic organic compound forming step (P-3) of the hydrophilic coating film forming method, the inorganic porous coating films 13a and 13b are covered with an organic coating liquid in such a way that the inorganic porous coating films 13a and 13b are not exposed from the surface of the hydrophilic organic compound 14. When forming the hydrophilic coating films 10A to 10D, the inorganic porous coating films 13a and 13b are buried by the hydrophilic organic compound 14. Therefore, it is possible to produce hydrophilic coating films 10A to 10D that allow the hydrophilic organic compound to exist for a long time.
[0128] In the water washing step (P-4) of the hydrophilic coating film formation method, excess hydrophilic organic compounds 14 that are fragilely bound to the voids 15 of the inorganic porous coating films 13a and 13b, except for those bound to the hydrophilic organic compounds 14 in the voids 15 (inorganic microparticles 16) of the inorganic porous coating films 13a and 13b and the surface 12 of the substrate 11, are removed from the hydrophilic coating films 10A to 10D. Therefore, hydrophilic organic compounds 14 that do not contribute to hydrophilicity can be produced, which are firmly bound to the voids 15 (inorganic microparticles 16) of the inorganic porous coating films 13a and 13b and the surface 12 of the substrate 11.
[0129] Hydrophilic coated films of 10A~10D produced by hydrophilic coating film formation method, such as... Figure 2 as well as Figure 3 , Figure 5 as well as Figure 6As shown, it is formed by inorganic porous coating membranes 13a and 13b having a large number of fine pores 15 of nanoscale size and hydrophilic organic compounds 14 (hydrophilic organic membranes) immersed in these pores 15 of inorganic porous coating membranes 13a and 13b.
[0130] Figure 2 In the hydrophilic coating film 10A shown, a hydrophilic organic compound 14 is immersed in a large number of nano-sized micropores 15 of an inorganic porous coating film 13a formed by adjacent, nearly spherical inorganic microparticles 16 partially linked together. The hydrophilic organic compound 14 (hydrophilic organic film) is bonded (joined) to the inorganic microparticles 16 forming the inorganic porous coating film 13a and the surface 12 of the substrate 11, and the hydrophilic organic compound 14 covers the surface of the inorganic porous coating film 13a, and the inorganic porous coating film 13a is embedded in the hydrophilic organic compound 14 (hydrophilic organic film).
[0131] Figure 3 In the hydrophilic coating film 10B shown, the hydrophilic organic compound 14 is immersed... Figure 1 In the numerous nano-sized micropores 15 of the inorganic porous coating film 13a, the hydrophilic organic compound 14 (hydrophilic organic film) is bonded (joined) to the inorganic microparticles 16 forming the inorganic porous coating film 13a and the surface 12 of the substrate 11, and the uppermost layer of the hydrophilic organic compound 14 is located slightly below the surface of the inorganic porous coating film 13a, and the uppermost layer of the inorganic porous coating film 13a (inorganic microparticles 16) is exposed upward from the uppermost layer of the hydrophilic organic compound 14 (hydrophilic organic film). Figure 3 In the hydrophilic coating film 10B, the portion of the inorganic porous coating film 13a (inorganic microparticles 16) that is exposed upward from the uppermost layer of the hydrophilic organic compound 14 (hydrophilic organic film) forms fine irregularities on the surface of the hydrophilic coating film 10B, and the portion forming the irregularities (uppermost layer) is coated with an extreme thin film formed by the hydrophilic organic compound 14 (hydrophilic organic film).
[0132] Figure 5 In the hydrophilic coating film 10C shown, the hydrophilic organic compound 14 is immersed... Figure 4 In the numerous nano-sized micropores 15 of the inorganic porous coating film 13b, the hydrophilic organic compound 14 (hydrophilic organic membrane) is bonded (joined) to the inorganic microparticles 16 forming the inorganic porous coating film 13a and the surface 12 of the substrate 11, and the hydrophilic organic compound 14 covers the surface of the inorganic porous coating film 13b, and the inorganic porous coating film 13b is embedded in the hydrophilic organic compound 14 (hydrophilic organic membrane).
[0133] Figure 6In the hydrophilic coating film 10D shown, the hydrophilic organic compound 14 is immersed... Figure 4 In the numerous nanoscale micropores 15 of the inorganic porous coating film 13b, the hydrophilic organic compound 14 (hydrophilic organic membrane) is bonded (joined) to the inorganic microparticles 16 forming the inorganic porous coating film 13a and the surface 12 of the substrate 11, and the uppermost layer of the hydrophilic organic compound 14 is located slightly below the surface of the inorganic porous coating film 13b, and the uppermost layer of the inorganic porous coating film 13b (inorganic microparticles 16) is exposed upward from the uppermost layer of the hydrophilic organic compound 14 (hydrophilic organic membrane). Figure 6 In the hydrophilic coating film 10D, the portion of the inorganic porous coating film 13b (inorganic microparticles 16) that is exposed upward from the uppermost layer of the hydrophilic organic compound 14 (hydrophilic organic film) forms fine irregularities on the surface of the hydrophilic coating film 10D, and the portion forming the irregularities (uppermost layer) is coated with an extreme thin film formed by the hydrophilic organic compound 14 (hydrophilic organic film).
[0134] In the hydrophilic coating films 10A to 10D, the porosity of the voids 15 formed in the inorganic porous coating films 13a and 13b is in the range of 20% to 70% relative to the volume of the inorganic porous coating films 13a and 13b. If the porosity of the voids 15 is less than 20%, there are fewer voids 15 formed in the inorganic porous coating films 13a and 13b, and the hydrophilicity and antifouling properties of the hydrophilic organic compound 14 (hydrophilic organic membrane) immersed in the voids 15 of the inorganic porous coating films 13a and 13b cannot be fully utilized. Therefore, the hydrophilic coating films 10A to 10D formed by the inorganic porous coating films 13a and 13b and the hydrophilic organic compound 14 cannot be endowed with excellent hydrophilicity and antifouling properties. When the porosity of the void 15 exceeds 70%, the inorganic porous coating films 13a and 13b become fragile, and the strength of the hydrophilic coating films 10A to 10D formed by the inorganic porous coating films 13a and 13b and the hydrophilic organic compound 14 (hydrophilic organic film) decreases, so the surface 12 of the substrate 11 cannot be adequately protected by the hydrophilic coating films 10A to 10D.
[0135] In the hydrophilic coating films 10A-10D, when the porosity of the voids 15 formed in the inorganic porous coating films 13a and 13b is within the aforementioned range, a sufficient number of fine voids 15 are formed in the inorganic porous coating films 13a and 13b. The hydrophilic organic compound 14 is immersed in these voids 15, and the excellent hydrophilicity and antifouling properties of the hydrophilic organic compound 14 (hydrophilic organic film) can be fully utilized. This can impart excellent hydrophilicity and antifouling properties to the hydrophilic coating films 10A-10D, and the hydrophilic coating films 10A-10D have sufficient strength to fully protect the coating surface 12 of the substrate 11.
[0136] In the hydrophilic coating films 10A-10D, the proportion of betaine polymer relative to the total mass of the hydrophilic organic compound 14 constituting the hydrophilic coating films 10A-10D is 20% or more. If the proportion of betaine polymer relative to the total mass of the hydrophilic organic compound 14 is less than 20%, the content of betaine polymer in the hydrophilic organic compound 14 is low, thus the hydrophilic function of the betaine polymer cannot be fully utilized. Therefore, the hydrophilic organic compound 14 prepared from the organic coating solution cannot exhibit sufficient hydrophilicity and antifouling properties, and cannot impart excellent hydrophilicity and antifouling properties to the hydrophilic coating films 10A-10D formed by the inorganic porous coating films 13a, 13b and the hydrophilic organic compound 14 (hydrophilic organic film).
[0137] In the hydrophilic coating films 10A-10D, since the proportion of betaine polymers having both cationic and anionic sites within the same molecule in the hydrophilic organic compound 14 is within the aforementioned range, the organic coating solution contains a sufficient amount of betaine polymer. This allows full utilization of the excellent hydrophilicity of the betaine polymer, and the hydrophilic organic compound 14 made from the organic coating solution exhibits sufficient hydrophilicity and antifouling properties. This imparts excellent hydrophilicity and antifouling properties to the hydrophilic coating films 10A-10D formed from the inorganic porous coating films 13a, 13b and the hydrophilic organic compound 14 (hydrophilic organic film).
[0138] The thickness of the hydrophilic coating films 10A to 10D is in the range of 0.01 μm to 3 μm, preferably in the range of 0.1 μm to 0.6 μm. If the thickness of the hydrophilic coating films 10A to 10D is less than 0.01 μm, the strength of the hydrophilic coating films 10A to 10D decreases, and thus the coating surface 12 of the substrate 11 cannot be adequately protected by the hydrophilic coating films 10A to 10D. When the thickness of the hydrophilic coating films 10A to 10D exceeds 3 μm, the film thickness becomes excessive, and the flexibility of the hydrophilic coating films 10A to 10D decreases, thus the hydrophilic coating films 10A to 10D cannot deform along with the coating surface 12 of the substrate 11.
[0139] Since the thickness of the hydrophilic coating films 10A-10D is within the specified range, the hydrophilic coating films 10A-10D can maintain the specified strength, and can fully protect the coating surface 12 of the substrate 11. Furthermore, the hydrophilic coating films 10A-10D have excellent flexibility and can deform along with the coating surface 12 of the substrate 11, thereby maintaining the coverage state of the hydrophilic coating films 10A-10D relative to the coating surface 12 of the substrate 11.
[0140] The inorganic porous coating films 13a and 13b constituting the hydrophilic coating films 10A to 10D contain at least one inorganic microparticle 16 selected from silicon dioxide (SiO2), aluminum oxide (Al2O3), zirconium dioxide (ZrO2), titanium dioxide (TiO2), and cerium dioxide (CeO2). In the case where the inorganic porous coating films 13a and 13b contain inorganic microparticles 16 containing silicon dioxide (SiO2), the hydrophilic organic compound 14 readily combines with the silicon dioxide. The hydrophilic organic compound 14, which penetrates the numerous micropores 15 of the inorganic porous coating films 13a and 13b, readily combines within the silicon dioxide-containing pores 15, thereby allowing the hydrophilic organic compound 14 (hydrophilic organic film) to be firmly bonded to the pores 15 of the inorganic porous coating films 13a and 13b.
[0141] In the case of inorganic microparticles 16 containing aluminum oxide (Al2O3) in the inorganic porous coating membranes 13a and 13b, the hydrophilic organic compound 14 can easily combine with the aluminum oxide. This allows the hydrophilic organic compound 14 (hydrophilic organic membrane) that has penetrated into the numerous micropores 15 of the inorganic porous coating membranes 13a and 13b to be firmly bound to the pores 15 containing aluminum oxide. Furthermore, due to the effect of aluminum oxide, salts such as magnesium, calcium, sodium, and silicon become difficult to adhere to the hydrophilic coating membranes 10A to 10D, thereby preventing contamination of the hydrophilic coating membranes 10A to 10D caused by the adhesion of salts such as magnesium, calcium, sodium, and silicon.
[0142] In the hydrophilic coating films 10A-10D, when the inorganic porous coating films 13a and 13b contain inorganic particles 16 of zirconium dioxide (ZrO2), the hardness of the inorganic porous coating films 13a and 13b can be improved, thereby enhancing the rigidity of the hydrophilic coating films 10A-10D. In the hydrophilic coating films 10A-10D, when the inorganic porous coating films 13a and 13b contain inorganic particles 16 of titanium dioxide (TiO2), the surface of the hydrophilic coating films 10A-10D is covered with hydrophilic groups by the action of light and water on the inorganic particles 16 of titanium dioxide, thereby imparting excellent self-cleaning effects to the hydrophilic coating films 10A-10D.
[0143] In the case of inorganic microparticles 16 containing cerium dioxide (CeO2) in the inorganic porous coating films 13a and 13b, the hardness can be improved by cerium dioxide, and the film can also have ultraviolet absorption capacity. Thus, the rigidity of the hydrophilic coating films 10A to 10D can be improved, and the film can also have ultraviolet absorption capacity.
[0144] Figure 8 To show the dripping on Figure 2 A diagram showing the contact angle θ of a water droplet W on a 10 Å hydrophilic coated film. Figure 9 To show the dripping on Figure 3 A diagram showing the contact angle θ of a water droplet W on a hydrophilic coated film 10B. Figure 10 To show the dripping on Figure 5 A diagram showing the contact angle θ of a water droplet W on a hydrophilic coated film at 10°C. Figure 11 To show the dripping on Figure 6 A diagram showing the contact angle θ of a water droplet W in a 10D hydrophilic coated film.
[0145] Figure 2 and Figure 3 , Figure 5 and Figure 6 In the hydrophilic coating films 10A-10D shown, the contact angle θ of the water droplet W is less than 10°. The contact angle θ of the water droplet W in the hydrophilic coating films 10A-10D is measured based on the JIS R3257 standard (Test Method for Wettability of Substrate Glass Surfaces). In the wettability test of the JIS R3257 standard, a test piece, a sample stage, an illumination device (light source), an optical reading device, and a syringe are prepared. The sample stage has a mechanism that allows the position of the sample stage to move up and down and left and right, so that the water droplet stationary on the test piece is located at the center of the optical axis of the illumination device and the optical reading device. The illumination device images the image of the water droplet on the test piece into the field of view of the optical reading device. The syringe has a capacity of 1 ml or less.
[0146] The conditions for the wettability test are: room temperature: 25±5℃, humidity: 50±10%, water droplet capacity: 1μl, measurement time: 30 seconds, and water used: distilled water. The operation sequence of the wettability test is as follows: (1) Calibrate the test apparatus according to the prescribed method. (2) Place the test pieces with hydrophilic coating films 10A and 10B on the test stage. (3) Add distilled water to a clean glass beaker and collect the distilled water using the syringe barrel. (4) Place the distilled water in the syringe as a droplet W on the test piece on the sample stage. Quickly measure the r and h of the droplet W. Or, read θ / 2. (5) The measurement positions should be at least 5.
[0147] Wettability is expressed as the average and standard deviation of data from more than 5 points at the contact angle θ, which is calculated based on the following (Equation 1), or obtained by directly reading θ / 2.
[0148] (Formula 1): θ=2tan -1 h / r
[0149] In Equation 1, r is the radius (mm) of the surface of the test piece that contacts the water droplet W, and h is the height (mm) from the surface of the test piece to the tip of the water droplet W.
[0150] In the hydrophilic coating membranes 10A~10D, since the contact angle θ of the water droplet W, measured according to the JIS R3257 standard, is less than 10°, they have excellent hydrophilicity and antifouling properties. The small contact angle between water and the surface of the hydrophilic coating membrane 10A~10D increases the contact area between water and the surface of the membrane. Thus, when the hydrophilic coating membrane 10A~10D is washed with water, the water comes into extensive contact with the surface of the membrane, making it easy to wash away dirt adhering to the hydrophilic coating membrane 10A~10D.
[0151] It should be noted that in the hydrophilic coating membranes 10B and 10D, the portion of the inorganic porous coating membrane 13b (inorganic microparticles 16) that protrudes upwards from the uppermost layer of the hydrophilic organic compound 14 (hydrophilic organic membrane) forms fine irregularities on the surface of the hydrophilic coating membranes 10B and 10D. Through these irregularities, the contact area with water can be further increased, so that the dirt adhering to the hydrophilic coating membranes 10B and 10D can be easily and reliably washed away by water.
[0152] In the hydrophilic coating films 10A to 10D, since the inorganic porous coating films 13a and 13b have an inorganic nanoporous structure prepared by using at least one of silica sol, alumina sol, zirconium dioxide sol, titanium dioxide sol, and cerium dioxide sol via a sol-gel method, the hydrophilic organic compound 14 penetrates into the numerous micropores 15 of the inorganic porous coating films 13a and 13b, and the hydrophilic organic compound 14 (hydrophilic organic film) is bonded (attached) to the inorganic porous coating film 13a and 13b. The gaps 15 (inorganic microparticles 16) in 3a and 13b and the surface 12 of the substrate 11 give the hydrophilic coating films 10A-10D excellent strength. Furthermore, the hydrophilic organic compounds 14 will not peel off or disappear prematurely from the hydrophilic coating films 10A-10D due to stress caused by the usage environment. This prevents the reduction of hydrophilicity and antifouling properties in the hydrophilic coating films 10A-10D and maintains the hydrophilic and antifouling functions brought by the hydrophilic organic compounds 14 for a long time.
[0153] In the hydrophilic coating membranes 10A-10D, the hydrophilic organic compound 14 contains a betaine polymer having both cationic and anionic sites within the same molecule. The hydrophilic organic compound 14 exhibits excellent hydrophilicity and antifouling properties, reliably reducing the contact angle between water and the membrane surface of the hydrophilic coating membranes 10A-10D, reliably increasing the contact area between water and the membrane surface of the hydrophilic coating membranes 10A-10D, and when the hydrophilic coating membranes 10A-10D are washed with water, water contacts the membrane surface of the hydrophilic coating membranes 10A-10D over a large area, making it easy to wash away dirt adhering to the hydrophilic coating membranes 10A-10D.
[0154] Figure 12 These are figures illustrating Examples 1 to 4 of the hydrophilic coated films 10A to 10D. Figure 13 The figures shown are from Examples 5 to 8, illustrating the hydrophilic coating films 10A to 10D. Figure 14 These are figures showing comparative examples 1 to 4 of the hydrophilic coated films. Figure 15 These are figures showing Comparative Examples 5 to 8, illustrating the hydrophilic coated films. Formation Figure 12 The inorganic porous coated films 13a and 13b of the hydrophilic coated films 10A-10D shown in Example 1 have a film thickness of 300 nm. An inorganic coating solution was used, containing silica nanoparticles with an average particle size of 55 nm and a solid content concentration of 1 wt%, and a silica sol solution with a solid content concentration of 0.5 wt%. The content of the hydrophilic organic compound 14 in the organic coating solution was 2 wt%, and the proportion of betaine polymer in the hydrophilic organic compound 14 was 30%.
[0155] The synthesis of hydrophilic organic compound 14 is described below. Under a nitrogen atmosphere, 9.9 mmol of 2-(methacryloyloxy)ethyl 2-(trimethylammonium)ethyl phosphate, 0.1 mmol of 3-mercaptopropyltrimethoxysilane, and water were added to a round-bottom flask to prepare a 20 wt% solution. Then, 0.1 mmol of 2,2'-azo (2-methyl-N-(2-hydroxyethyl)propionamide) was added, and the mixture was stirred and heated at 55°C for 3 hours to obtain a betaine polymer solution. Similarly, 9.9 mmol of 2-hydroxyethyl methacrylate, 0.1 mmol of 3-mercaptopropyltrimethoxysilane, and water were added to prepare a 20 wt% solution. Then, 0.1 mmol of 2,2'-azo (2-methyl-N-(2-hydroxyethyl)propionamide) was added, and the mixture was stirred and heated at 55°C for 3 hours to obtain a hydrophilic polymer solution. They were mixed and water was added to obtain a 2wt% hydrophilic coating solution containing 30% betaine polymer.
[0156] Both inorganic and organic coating solutions were applied using a fabric coating method via microfibers. Scanning electron microscopes (SEMs) were used: an XVision200TB from SII NanoTechnology Co., Ltd., and a JSM-5500 from NEC Corporation. Cross-sectional SEM observation confirmed a film thickness of 300 nm. Furthermore, surface SEM observation revealed a porosity of 42%.
[0157] The inorganic porous coated films 13a and 13b of the hydrophilic coated films 10A to 10D shown in Example 2 have a film thickness of 300 nm. An inorganic coating solution containing silica nanoparticles with an average particle size of 55 nm and a solid content concentration of 5 wt% and a silica sol solution with a solid content concentration of 2.5 wt% was used. The content of hydrophilic organic compound 14 in the organic coating solution is 2 wt%, and the proportion of betaine polymer in hydrophilic organic compound 14 is 35%.
[0158] The synthesis of hydrophilic organic compound 14 is described below. Under a nitrogen atmosphere, 9.9 mmol of 3-((2-(methacryloyloxy)ethyl)dimethylammonium)propane-1-sulfonate, 0.1 mmol of 3-mercaptopropyltrimethoxysilane, and water were added to a round-bottom flask to prepare a 20 wt% solution. Then, 0.1 mmol of 2,2'-azo(2-methyl-N-(2-hydroxyethyl)propionamide) was added, and the mixture was stirred and heated at 55°C for 3 hours to obtain a betaine polymer solution. Similarly, 10 mmol of N-isopropylacrylamide and water were added to prepare a 20 wt% solution. Then, 0.1 mmol of 2,2'-azo(2-methyl-N-(2-hydroxyethyl)propionamide) was added, and the mixture was stirred and heated at 55°C for 3 hours to obtain a hydrophilic polymer solution.
[0159] The inorganic and organic coating solutions were coated using a fabric coating method via microfibers. They were mixed and water was added to obtain a 2 wt% hydrophilic coating solution containing 35% betaine polymer. Cross-sectional SEM observation revealed a film thickness of 300 nm, and surface SEM observation revealed a porosity of 28%.
[0160] The inorganic porous coated films 13a and 13b, which form the hydrophilic coated films 10A-10D shown in Example 3, have a film thickness of 200 nm. An inorganic coating solution containing silica nanoparticles with an average particle size of 12 nm and a solid content concentration of 10 wt% and a silica sol solution with a solid content concentration of 5 wt% was used. The content of the hydrophilic organic compound 14 in the organic coating solution was 2 wt%, and the proportion of betaine polymer in the hydrophilic organic compound 14 was 30%.
[0161] The synthesis of hydrophilic organic compound 14 is described below. Under a nitrogen atmosphere, 10 mmol of 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate and water were added to a round-bottom flask to prepare a 20 wt% solution. Next, 0.1 mmol of 2,2'-azo(2-methyl-N-(2-hydroxyethyl)propionamide) was added, and the mixture was stirred and heated at 55°C for 3 hours to obtain a betaine polymer solution. Similarly, 10.0 mmol of 2-hydroxyethyl methacrylate and water were added to prepare a 20 wt% solution. Next, 0.1 mmol of 2,2'-azo(2-methyl-N-(2-hydroxyethyl)propionamide) was added, and the mixture was stirred and heated at 55°C for 3 hours to obtain a hydrophilic polymer solution. These solutions were mixed, and water was added to obtain a 2 wt% hydrophilic coating solution containing 30% betaine polymer.
[0162] Both the inorganic and organic coating solutions were coated using a fabric coating method via microfibers. Cross-sectional SEM observation revealed a film thickness of 200 nm, and surface SEM observation showed a porosity of 52%.
[0163] The inorganic porous coated films 13a and 13b, which form the hydrophilic coated films 10A-10D shown in Example 4, have a film thickness of 150 nm. An inorganic coating solution containing silica nanoparticles with an average particle size of 20 nm and a solid content concentration of 2 wt% and a silica sol solution with a solid content concentration of 1 wt% was used. The content of the hydrophilic organic compound 14 in the organic coating solution was 2 wt%, and the proportion of betaine polymer in the hydrophilic organic compound 14 was 30%.
[0164] The synthesis of hydrophilic organic compound 14 is described below. Under a nitrogen atmosphere, 9.9 mmol of 3-[(3-acrylamidopropyl)dimethylammonium]propionate, 0.1 mmol of 3-mercaptopropyltrimethoxysilane, and water were added to a round-bottom flask to prepare a 20 wt% solution. Then, 0.1 mmol of 2,2'-azo (2-methyl-N-(2-hydroxyethyl)propionamide) was added, and the mixture was stirred and heated at 55°C for 3 hours to obtain a betaine polymer solution. Similarly, 9.9 mmol of N-isopropylacrylamide, 0.1 mmol of 3-mercaptopropyltrimethoxysilane, and water were added to prepare a 20 wt% solution. Then, 0.1 mmol of 2,2'-azo (2-methyl-N-(2-hydroxyethyl)propionamide) was added, and the mixture was stirred and heated at 55°C for 3 hours to obtain a hydrophilic polymer solution. They were mixed and water was added to obtain a 2 wt% hydrophilic coating solution containing 30% betaine polymer.
[0165] Both the inorganic and organic coating solutions were coated using a fabric coating method via microfibers. Cross-sectional SEM observation revealed a film thickness of 150 nm, and surface SEM observation showed a porosity of 65%.
[0166] The inorganic porous coated films 13a and 13b, which form the hydrophilic coated films 10A-10D shown in Example 5, have a film thickness of 250 nm. An inorganic coating solution containing silica nanoparticles with an average particle size of 12 nm and a solid content concentration of 5 wt% and a silica sol solution with a solid content concentration of 2.5 wt% were used. The content of the hydrophilic organic compound 14 in the organic coating solution was 2 wt%, and the proportion of betaine polymer in the hydrophilic organic compound 14 was 100%.
[0167] The synthesis of hydrophilic organic compound 14 is described below. Under a nitrogen atmosphere, 10 mmol of 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate and water were added to a flask to prepare a 20 wt% solution. Next, 0.1 mmol of 2,2'-azo (2-methyl-N-(2-hydroxyethyl)propionamide) was added, and the mixture was stirred and heated at 55°C for 3 hours to obtain a betaine polymer solution. Water was added to this solution to obtain a 2 wt% hydrophilic coating solution containing 100% betaine polymer. Both the inorganic and organic coating solutions were coated using a fabric coating method via microfibers. Cross-sectional SEM observation revealed a film thickness of 250 nm, and surface SEM observation showed a porosity of 44%.
[0168] The inorganic porous coated films 13a and 13b, which form the hydrophilic coated films 10A-10D shown in Example 6, have a film thickness of 320 nm. An inorganic coating solution containing alumina nanoparticles with an average particle size of 30 nm and a solid content concentration of 5 wt% and an alumina sol solution with a solid content concentration of 2.5 wt% were used. The content of the hydrophilic organic compound 14 in the organic coating solution was 2 wt%, and the proportion of betaine polymer in the hydrophilic organic compound 14 was 100%.
[0169] The synthesis of hydrophilic organic compound 14 is described below. Under a nitrogen atmosphere, 10 mmol of 3-[(3-acrylamidopropyl)dimethylammonium]propionate and water were added to a flask to prepare a 20 wt% solution. Next, 0.1 mmol of 2,2'-azo (2-methyl-N-(2-hydroxyethyl)propionamide) was added, and the mixture was stirred and heated at 55°C for 3 hours to obtain a betaine polymer solution. Water was added to this solution to obtain a 2 wt% hydrophilic coating solution containing 100% betaine polymer.
[0170] Both the inorganic and organic coating solutions were coated using a fabric coating method via microfibers. Cross-sectional SEM observation revealed a film thickness of 320 nm, and surface SEM observation showed a porosity of 48%.
[0171] The inorganic porous coated films 13a and 13b of the hydrophilic coated films 10A-10D shown in Example 7 have a film thickness of 180 nm. An inorganic coating solution containing zirconium dioxide nanoparticles with an average particle size of 12 nm and a solid content concentration of 5 wt% and a zirconium dioxide sol solution with a solid content concentration of 2.5 wt% was used. The content of the hydrophilic organic compound 14 in the organic coating solution was 2 wt%, and the proportion of betaine polymer in the hydrophilic organic compound 14 was 100%.
[0172] The synthesis of hydrophilic organic compound 14 is described below. Under a nitrogen atmosphere, 10 mmol of 2-(methacryloyloxy)ethyl 2-(trimethylammonium)ethyl phosphate and water were added to a round-bottom flask to prepare a 20 wt% solution. Next, 0.1 mmol of 2,2'-azo (2-methyl-N-(2-hydroxyethyl)propionamide) was added, and the mixture was stirred and heated at 55°C for 3 hours to obtain a betaine polymer solution. Water was added to this solution to obtain a 2 wt% hydrophilic coating solution containing 100% betaine polymer.
[0173] Both the inorganic and organic coating solutions were coated using a fabric coating method via microfibers. Cross-sectional SEM observation revealed a film thickness of 180 nm, and surface SEM observation showed a porosity of 52%.
[0174] The inorganic porous coated films 13a and 13b, forming the hydrophilic coated films 10A-10D shown in Example 8, have a film thickness of 220 nm. An inorganic coating solution containing silica nanoparticles with an average particle size of 12 nm and a solid content concentration of 5 wt% and silica nanosol with a solid content concentration of 2.5 wt% was used. The content of the hydrophilic organic compound 14 in the organic coating solution was 2 wt%, and the proportion of betaine polymer in the hydrophilic organic compound 14 was 100%.
[0175] The synthesis of hydrophilic organic compound 14 is described below. Under a nitrogen atmosphere, 9.9 mmol of 3-((2-(methacryloyloxy)ethyl)dimethylammonium)propane-1-sulfonate, 0.1 mmol of 3-mercaptopropyltrimethoxysilane, and water were added to a flask to prepare a 20 wt% solution. Next, 0.1 mmol of 2,2'-azo(2-methyl-N-(2-hydroxyethyl)propionamide) was added, and the mixture was stirred and heated at 55°C for 3 hours to obtain a betaine polymer solution. Water was added to this solution to obtain a 2 wt% hydrophilic coating solution containing 100% betaine polymer.
[0176] Both the inorganic and organic coating solutions were coated using a fabric coating method via microfibers. Cross-sectional SEM observation revealed a film thickness of 220 nm, and surface SEM observation showed a porosity of 47%.
[0177] In the hydrophilic coating films 10A-10D shown in Examples 1-4, the contact angle θ of water droplets W when the coating film 10A-10D is first formed on the coating surface 12 of the substrate 11 is ○ (20° or less, good) or ◎ (10° or less, even better). After half a year from when the coating film 10A-10D is formed on the coating surface 12 of the substrate 11, the contact angle θ of water droplets W is ○ (20° or less, good) or ◎ (10° or less, even better). The transparency of the coating film 10A-10D is ○ (no turbidity, good).
[0178] form Figure 14 The inorganic porous coating membrane shown in Comparative Example 1 has a thickness of 3000 nm for the hydrophilic coating. An inorganic coating solution was used, comprising silica sol solutions with solid content concentrations of 3 wt% and 1.5 wt% respectively, prepared by mixing silica nanoparticles with average particle sizes of 1500 nm, 60 nm, and 12 nm. The organic coating solution contained 2 wt% hydrophilic organic compounds, of which betaine polymer accounted for 30%.
[0179] The synthesis of hydrophilic organic compound 14 is described below. Under a nitrogen atmosphere, 9.9 mmol of 2-(methacryloyloxy)ethyl 2-(trimethylammonium)ethyl phosphate, 0.1 mmol of 3-mercaptopropyltrimethoxysilane, and water were added to a round-bottom flask to prepare a 20 wt% solution. Then, 0.1 mmol of 2,2'-azo (2-methyl-N-(2-hydroxyethyl)propionamide) was added, and the mixture was stirred and heated at 55°C for 3 hours to obtain a betaine polymer solution. Similarly, 9.9 mmol of 2-hydroxyethyl methacrylate, 0.1 mmol of 3-mercaptopropyltrimethoxysilane, and water were added to prepare a 20 wt% solution. Then, 0.1 mmol of 2,2'-azo (2-methyl-N-(2-hydroxyethyl)propionamide) was added, and the mixture was stirred and heated at 55°C for 3 hours to obtain a hydrophilic polymer solution. They were mixed and water was added to obtain a 2wt% hydrophilic coating solution containing 30% betaine polymer.
[0180] The coating method for both inorganic and organic coating solutions was spin coating. Immediately after coating, cross-sectional SEM observation revealed a film thickness of 3000 nm, and surface SEM observation showed a porosity of 18%. The results for the hydrophilic coating film shown in Comparative Example 1 were as follows: when the coating film was first formed on the surface 12 of the substrate 11, the contact angle θ of the water droplet W was × (exceeding 20°, undesirable); six months after the coating film formed on the surface 12 of the substrate 11, the contact angle θ of the water droplet W was × (exceeding 20°, undesirable).
[0181] form Figure 14 The inorganic porous coating film of Comparative Example 2, which is a hydrophilic coating film, has a film thickness of 1000 nm. An inorganic coating solution containing silica nanoparticles with an average particle size of 55 nm and a solid content concentration of 3 wt% and a silica sol solution with a solid content concentration of 1.5 wt% was used. No organic coating solution was applied. Both the inorganic and organic coating solutions were applied using a fabric coating method via microfibers. Immediately after coating, cross-sectional SEM observation revealed a film thickness of 1000 nm, and surface SEM observation showed a porosity of 44%. The results for the hydrophilic coating film of Comparative Example 2 show that, after six months from the formation of the coating film on the surface 12 of the substrate 11, the contact angle θ of water droplets W was × (exceeding 20°, which is undesirable).
[0182] form Figure 14 Comparative Example 3 shows an inorganic porous coating membrane with a thickness of 10,000 nm for the hydrophilic coating. The inorganic coating solution used contained silica nanoparticles with an average particle size of 55 nm and a solid content concentration of 3 wt%, and a silica sol solution with a solid content concentration of 1.5 wt%. The organic coating solution contained 2 wt% hydrophilic organic compounds, of which 30% were betaine polymers.
[0183] The synthesis of hydrophilic organic compound 14 is described below. Under a nitrogen atmosphere, 9.9 mmol of 3-((2-(methacryloyloxy)ethyl)dimethylammonium)propane-1-sulfonate, 0.1 mmol of 3-mercaptopropyltrimethoxysilane, and water were added to a round-bottom flask to prepare a 20 wt% solution. Next, 0.1 mmol of 2,2'-azo(2-methyl-N-(2-hydroxyethyl)propionamide) was added, and the mixture was stirred and heated at 55°C for 3 hours to obtain a betaine polymer solution. Similarly, 10 mmol of N-isopropylacrylamide and water were added to prepare a 20 wt% solution. Next, 0.1 mmol of 2,2'-azo(2-methyl-N-(2-hydroxyethyl)propionamide) was added, and the mixture was stirred and heated at 55°C for 3 hours to obtain a hydrophilic polymer solution. These solutions were mixed, and water was added to obtain a 2 wt% hydrophilic coating solution containing 30% betaine polymer.
[0184] The inorganic and organic coating solutions were coated using a fabric coating method via microfibers. Cross-sectional SEM observation revealed a film thickness of 10000 nm, and surface SEM observation showed a porosity of 52%. The hydrophilic coating film shown in Comparative Example 3 had a transparency of × (turbidity, poor).
[0185] form Figure 14 Comparative Example 4 shows an inorganic porous coating membrane with a thickness of 10,000 nm for the hydrophilic coating. An inorganic coating solution was used, containing silica nanoparticles with an average particle size of 55 nm and a solid content concentration of 0.2 wt%, and a silica sol solution with a solid content concentration of 0.1 wt%. The organic coating solution contained 2 wt% hydrophilic organic compounds, of which 30% were betaine polymers.
[0186] The synthesis of hydrophilic organic compound 14 is described below. Under a nitrogen atmosphere, 10 mmol of 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate and water were added to a round-bottom flask to prepare a 20 wt% solution. Next, 0.1 mmol of 2,2'-azo(2-methyl-N-(2-hydroxyethyl)propionamide) was added, and the mixture was stirred and heated at 55°C for 3 hours to obtain a betaine polymer solution. Similarly, 10.0 mmol of 2-hydroxyethyl methacrylate and water were added to prepare a 20 wt% solution. Next, 0.1 mmol of 2,2'-azo(2-methyl-N-(2-hydroxyethyl)propionamide) was added, and the mixture was stirred and heated at 55°C for 3 hours to obtain a hydrophilic polymer solution. These solutions were mixed, and water was added to obtain a 2 wt% hydrophilic coating solution containing 30% betaine polymer.
[0187] The inorganic and organic coating solutions were coated using a fabric coating method via microfibers. Cross-sectional SEM observation revealed a film thickness of 10000 nm, and surface SEM observation showed a porosity of 75%. Comparative Example 4 showed the following results for the hydrophilic coating film: when the coating film was first formed on the surface 12 of the substrate 11, the contact angle θ of the water droplet W was × (exceeding 20°, defective); six months after the coating film was formed on the surface 12 of the substrate 11, the contact angle θ of the water droplet W was × (exceeding 20°, defective); and the transparency of the coating film was × (turbidity, defective).
[0188] form Figure 15 Comparative Example 5 shows an inorganic porous coating membrane with a thickness of 500 nm for the hydrophilic coating. An inorganic coating solution containing silica nanoparticles with an average particle size of 12 nm and a solid content concentration of 60 wt% and a silica sol solution with a solid content concentration of 30 wt% was used. The organic coating solution contained 2 wt% hydrophilic organic compounds, of which 30% were betaine polymers.
[0189] The synthesis of hydrophilic organic compound 14 is described below. Under a nitrogen atmosphere, 9.9 mmol of 3-[(3-acrylamidopropyl)dimethylammonium]propionate, 0.1 mmol of 3-mercaptopropyltrimethoxysilane, and water were added to a round-bottom flask to prepare a 20 wt% solution. Then, 0.1 mmol of 2,2'-azo (2-methyl-N-(2-hydroxyethyl)propionamide) was added, and the mixture was stirred and heated at 55°C for 3 hours to obtain a betaine polymer solution. Similarly, 9.9 mmol of N-isopropylacrylamide, 0.1 mmol of 3-mercaptopropyltrimethoxysilane, and water were added to prepare a 20 wt% solution. Then, 0.1 mmol of 2,2'-azo (2-methyl-N-(2-hydroxyethyl)propionamide) was added, and the mixture was stirred and heated at 55°C for 3 hours to obtain a hydrophilic polymer solution. They were mixed and water was added to obtain a 2 wt% hydrophilic coating solution containing 30% betaine polymer.
[0190] The inorganic and organic coating solutions were coated using a fabric coating method via microfibers. Cross-sectional SEM observation revealed a film thickness of 500 nm, and surface SEM observation showed a porosity of 38%. The hydrophilic coating film shown in Comparative Example 5 had a transparency of × (turbidity, poor).
[0191] form Figure 15 Comparative Example 6 shows an inorganic porous coating membrane with a thickness of 350 nm for the hydrophilic coating. An inorganic coating solution was used containing silica nanoparticles with an average particle size of 200 nm and a solid content concentration of 3 wt%, and a silica sol solution with a solid content concentration of 1.5 wt%. The organic coating solution contained 2 wt% hydrophilic organic compounds, of which 30% were betaine polymers.
[0192] The synthesis of hydrophilic organic compound 14 is described below. Under a nitrogen atmosphere, 9.9 mmol of 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate, 0.1 mmol of 3-mercaptopropyltrimethoxysilane, and water were added to a round-bottom flask to prepare a 20 wt% solution. Then, 0.1 mmol of 2,2'-azo (2-methyl-N-(2-hydroxyethyl)propionamide) was added, and the mixture was stirred and heated at 55°C for 3 hours to obtain a betaine polymer solution. Similarly, 9.9 mmol of N-isopropylacrylamide, 0.1 mmol of 3-mercaptopropyltrimethoxysilane, and water were added to prepare a 20 wt% solution. Then, 0.1 mmol of 2,2'-azo (2-methyl-N-(2-hydroxyethyl)propionamide) was added, and the mixture was stirred and heated at 55°C for 3 hours to obtain a hydrophilic polymer solution. They were mixed and water was added to obtain a 2 wt% hydrophilic coating solution containing 30% betaine polymer.
[0193] The inorganic and organic coating solutions were coated using a fabric coating method via microfibers. Cross-sectional SEM observation revealed a film thickness of 350 nm, and surface SEM observation showed a porosity of 44%. The hydrophilic coating film shown in Comparative Example 6 had a transparency of × (turbidity, poor).
[0194] form Figure 15 Comparative Example 7 shows an inorganic porous coating membrane with a thickness of 300 nm for the hydrophilic coating. An inorganic coating solution was used containing silica nanoparticles with an average particle size of 55 nm and a solid content concentration of 1 wt%, and a silica sol solution with a solid content concentration of 0.5 wt%. The organic coating solution contained 0.02 wt% hydrophilic organic compounds, of which betaine polymer comprised 30%.
[0195] The synthesis of hydrophilic organic compound 14 is described below. Under a nitrogen atmosphere, 9.9 mmol of 3-[(3-acrylamidopropyl)dimethylammonium]propionate, 0.1 mmol of 3-mercaptopropyltrimethoxysilane, and water were added to a round-bottom flask to prepare a 20 wt% solution. Then, 0.1 mmol of 2,2'-azo (2-methyl-N-(2-hydroxyethyl)propionamide) was added, and the mixture was stirred and heated at 55°C for 3 hours to obtain a betaine polymer solution. Similarly, 9.9 mmol of N-isopropylacrylamide, 0.1 mmol of 3-mercaptopropyltrimethoxysilane, and water were added to prepare a 20 wt% solution. Then, 0.1 mmol of 2,2'-azo (2-methyl-N-(2-hydroxyethyl)propionamide) was added, and the mixture was stirred and heated at 55°C for 3 hours to obtain a hydrophilic polymer solution. They were mixed and water was added to obtain a 2 wt% hydrophilic coating solution containing 30% betaine polymer.
[0196] The inorganic and organic coating solutions were coated using a fabric coating method via microfibers. Cross-sectional SEM observation revealed a film thickness of 300 nm, and surface SEM observation showed a porosity of 51%. Comparative Example 7 showed that the contact angle θ of water droplets W immediately upon formation on the surface 12 of the substrate 11 was × (exceeding 20°, undesirable). After six months from the formation of the coating on the surface 12 of the substrate 11, the contact angle θ of water droplets W was × (exceeding 20°, undesirable), and the transparency of the coating was × (turbidity present, undesirable).
[0197] form Figure 15 Comparative Example 8 shows an inorganic porous coating membrane with a thickness of 240 nm for the hydrophilic coating. An inorganic coating solution was used, containing silica nanosol solutions with solid content concentrations of 5 wt% and 2.5 wt% respectively, prepared by mixing silica nanoparticles with average particle sizes of 1500 nm, 60 nm, and 12 nm. The organic coating solution contained 2 wt% hydrophilic organic compounds, with betaine polymer comprising 100% of the hydrophilic organic compounds.
[0198] The synthesis of hydrophilic organic compound 14 is described below. Under a nitrogen atmosphere, 10 mmol of 3-((2-(methacryloyloxy)ethyl)dimethylammonium)propane-1-sulfonate and water were added to a round-bottom flask to prepare a 20 wt% solution. Next, 0.1 mmol of 2,2'-azo(2-methyl-N-(2-hydroxyethyl)propionamide) was added, and the mixture was stirred and heated at 55°C for 3 hours to obtain a betaine polymer solution. Water was added to this solution to obtain a 2 wt% hydrophilic coating solution containing 100% betaine polymer.
[0199] The inorganic and organic coating solutions were coated using a fabric coating method via microfibers. Immediately after coating, cross-sectional SEM observation revealed a film thickness of 240 nm, and surface SEM observation showed a porosity of 18%. Comparative Example 8 showed that the contact angle θ of water droplets W immediately upon coating formation on the surface 12 of substrate 11 was × (exceeding 20°, undesirable). After six months from the formation of the coating on the coated surface 12 of substrate 11, the contact angle θ of water droplets W was also × (exceeding 20°, undesirable).
[0200] It can be seen that in the hydrophilic coating films 10A-10D shown in Examples 1-8, the film thickness, the concentration of solid components of inorganic microparticles 16, the average particle size of inorganic microparticles 16, the content of hydrophilic organic compounds, and the proportion of betaine polymer in the hydrophilic organic compounds are all within the numerical range of the present invention. The contact angle θ of water droplets W when the coating films 10A-10D are first formed on the coating surface 12 of the substrate 11, and the contact angle θ of water droplets W after six months from the formation of the coating films 10A-10D on the coating surface 12 of the substrate 11, are also within the numerical range of the present invention. The transparency of all samples is good. In contrast, the results of the hydrophilic coating films shown in Comparative Examples 1 to 8 are as follows: the film thickness, the concentration of solid components of inorganic microparticles 16, the average particle size of inorganic microparticles 16, the content of hydrophilic organic compounds, and the proportion of betaine polymer in the hydrophilic organic compounds are all outside the numerical range of the present invention. At least one of the following is poor: the contact angle θ of water droplets W when the coating film is first formed on the coating surface 12 of the substrate 11, the contact angle θ of water droplets W after half a year from the formation of the coating film on the coating surface 12 of the substrate 11, and the transparency of the coating film. Explanation of reference numerals in the attached figures
[0201] 10A~10D: Hydrophilic coating film; 11: Substrate; 12: Surface (surface, inner surface); 13a: Inorganic porous coating film; 13b: Inorganic porous coating film; 14: Hydrophilic organic compound; 15: Void; 16: Inorganic microparticles.
Claims
1. A hydrophilic coated film, characterized by, It is formed by an inorganic porous coating membrane with a large number of pores of nanoscale size and a hydrophilic organic compound immersed in the pores of the inorganic porous coating membrane, and the water contact angle is less than 20° as measured based on the JIS R3257 standard.
2. The hydrophilic coated film according to claim 1, characterized in that, The water contact angle measured based on the JIS R3257 standard is less than 10°.
3. The hydrophilic coated film according to claim 1, wherein The inorganic porous coating film contains at least one inorganic microparticle selected from silicon dioxide (SiO2), aluminum oxide (Al2O3), zirconium dioxide (ZrO2), titanium dioxide (TiO2), and cerium dioxide (CeO2).
4. The hydrophilic coated film according to claim 1, wherein The inorganic porous coating film has an inorganic nanoporous structure, which is prepared by using at least one of silica sol, alumina sol, zirconium dioxide sol, titanium dioxide sol, and cerium dioxide sol via a sol-gel method.
5. The hydrophilic coated film according to claim 1, wherein The hydrophilic organic compound contains a betaine polymer having both cationic and anionic sites within the same molecule.
6. The hydrophilic coated film according to claim 5, wherein The proportion of betaine polymer in the hydrophilic organic compound is more than 20%.
7. The hydrophilic coated film according to claim 1, wherein The porosity of the voids formed in the inorganic porous coating film is in the range of 20% to 70% relative to the volume of the inorganic porous coating film.
8. The hydrophilic coated film according to claim 1, wherein The thickness of the hydrophilic coating film is in the range of 0.01~3μm.
9. The hydrophilic coated film according to claim 1, wherein The hydrophilic organic compound penetrates the pores of the inorganic porous coating membrane and covers the surface of the inorganic porous coating membrane.
10. The hydrophilic coated film according to claim 1, wherein The uppermost layer of the hydrophilic organic compound is located slightly below the surface of the inorganic porous coating film. The portion of the inorganic porous coating film exposed upward from the uppermost layer of the hydrophilic organic compound is coated with an extreme thin film formed by the hydrophilic organic compound, and fine irregularities are formed on the surface of the hydrophilic coating film.
11. A hydrophilic coating solution characterized in that, The coating is formed by an inorganic coating liquid and an organic coating liquid. The inorganic coating liquid produces an inorganic porous coating membrane with a large number of pores of nanoscale size. The organic coating liquid produces a hydrophilic organic compound containing a betaine polymer having cationic and anionic sites within the same molecule. The organic compound covers the inorganic porous coating membrane while being immersed in the pores of the inorganic porous coating membrane.
12. The hydrophilic coating solution of claim 11, wherein, The proportion of betaine polymer in the hydrophilic organic compound is more than 20%.
13. The hydrophilic coating solution of claim 11, wherein The inorganic coating solution contains at least one inorganic microparticle selected from silicon dioxide (SiO2), aluminum oxide (Al2O3), zirconium dioxide (ZrO2), titanium dioxide (TiO2), and cerium dioxide (CeO2). The solid content concentration of the inorganic microparticles in the inorganic coating solution is 0.3~50 wt%.
14. The hydrophilic coating solution of claim 13, wherein, The inorganic coating liquid contains inorganic microparticles with an average particle size of less than 1 μm.
15. The hydrophilic coating solution of claim 11, wherein, The content of hydrophilic organic compounds in the organic coating solution is in the range of 0.1 to 20 wt% relative to the total weight of the organic coating solution.
16. A hydrophilic coating film forming method of producing a hydrophilic coating film formed of an inorganic porous coating film having a large number of voids of nanometer size and a hydrophilic organic compound, characterized by comprising: a washing step of washing a surface of a prescribed substrate with an alkaline detergent and then washing the surface of the substrate with an acidic liquid; an inorganic porous coating film forming step of applying an inorganic coating liquid containing inorganic microparticles to the surface of the substrate and forming the inorganic porous coating film having the inorganic nano-porous structure with a large number of voids of nanometer size by a sol-gel method; a hydrophilic organic compound forming step of applying an organic coating liquid containing a betaine polymer having a cationic site and an anionic site in the same molecule to the surface of the substrate, and forming the hydrophilic organic compound containing the betaine polymer on the surface of the substrate in a state where the organic coating liquid is immersed in the voids of the inorganic porous coating film; and a water washing step of washing the surface of the hydrophilic coating film formed of the inorganic porous coating film and the hydrophilic organic compound with water. In the inorganic porous coating film forming step, the inorganic porous coating film having the inorganic nano-porous structure is formed by a sol-gel method using at least one of a silica sol, an alumina sol, a zirconia sol, a titania sol, and a ceria sol. In the hydrophilic organic compound forming step, the inorganic porous coating film is coated with the organic coating liquid in such a manner that the inorganic porous coating film does not protrude from the surface of the hydrophilic organic compound, so that the inorganic porous coating film is buried in the hydrophilic organic compound when the hydrophilic coating film is formed.
17. The hydrophilic coated film forming method according to claim 16, wherein In the hydrophilic organic compound forming step, the inorganic porous coating liquid is applied to the surface of the substrate in such a manner that the inorganic porous coating film protrudes upward from the uppermost layer of the hydrophilic organic compound in a state where the inorganic coating liquid is located slightly below the surface of the inorganic porous coating film, so that the inorganic porous coating film protrudes upward from the uppermost layer of the hydrophilic organic compound when the hydrophilic coating film is formed, the portion of the inorganic porous coating film protruding upward from the uppermost layer of the hydrophilic organic compound is coated with an extremely thin film formed of the hydrophilic organic compound, and a fine unevenness is formed on the surface of the hydrophilic coating film.
18. The hydrophilic coating film formation method according to claim 16, wherein In the water washing step, the hydrophilic organic compound weakly bound to the voids of the inorganic porous coating film is washed away by water, so that the hydrophilic organic compound not contributing to hydrophilicity is removed from the hydrophilic coating film.
19. The hydrophilic coating film formation method according to claim 16, wherein 20. The hydrophilic coated film forming method according to claim 16, wherein
Citation Information
Patent Citations
Hydrophilic coating film and article having the same, and method for forming hydrophilic coating film
JP2019089930A
Polymerizable composition, and hydrophilic treatment method
JP2022129100A
